Recombinant spider silk extrudate preparations

JP7640107B2Active Publication Date: 2025-03-05BOLT THREADS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022501154
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-12
Filing Date
2020-07-11
Publication Date
2025-03-05
Estimated Expiration
2040-07-11

Smart Images

  • Figure 0007640107000026
    Figure 0007640107000026
  • Figure 0007640107000027
    Figure 0007640107000027
  • Figure 0007640107000028
    Figure 0007640107000028
Patent Text Reader

Abstract

[0003] Disclosed herein are recombinant spider silk compositions formed from silk-based extrudates, such as stable films that adhere to skin, and methods for making these compositions. In some embodiments, provided herein are methods for making a silk-based emulsion, the methods comprising: applying pressure and shear to a composition comprising recombinant spider silk polypeptide powder and glycerol to mix the composition, thereby converting the composition into an extrudate; suspending at least a portion of the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and mixing the aqueous extrudate suspension into an emulsion to form the silk-based emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 62 / 873,395, filed July 12, 2019, and U.S. Provisional Application No. 62 / 975,647, filed February 12, 2020, the entire contents of which are incorporated herein by reference.

[0002] FIELD OF THEINVENTION The present disclosure relates to recombinant spider silk compositions formed from silk-based extrudates, such as stable films that adhere to the skin. [Background technology]

[0003] 2. Background of the Invention Silk is a structural protein that combines many desirable properties for use in skin care products and cosmetics. Recent technology has allowed for the derivation of recombinant spider silk polypeptides using a variety of host organisms, allowing for the scale-up of production of a variety of recombinant spider silk polypeptides and polypeptides. However, it is difficult to solubilize the collected silk powder into a solution to obtain a desired formulation, making it difficult to achieve a solid or gel composition based on full-length silk.

[0004] Most cosmetics and skin care products incorporating silk attempt to solve the solubility problem by hydrolyzing silk into small amino acid chains. However, these compositions containing degraded silk protein fragments lose the desirable properties of silk. Furthermore, the use of harmful solvents makes silk formulations that are intended to come into contact with the skin unsuitable for use.

[0005] Although novel methods for producing sericin-depleted silkworm silk (referred to herein as "silk fibroin") have managed to lead to a variety of skin care products incorporating full-length (i.e., non-hydrolyzed) silk proteins, the self-aggregation properties of silk affect the shelf stability of these products. Specifically, full-length silk fibroin molecules tend to aggregate and precipitate from solution. Moreover, these processes are not scalable for commercial use.

[0006] Recombinant spider silk polypeptides form similar secondary and tertiary structures as silk fibroin, making them similarly desirable for use in cosmetic and skin care formulations, but can pose similar stability and solubility problems due to their tendency to self-aggregate. Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, there is a need for a scalable method to increase the solubility and stability of recombinant spider silk polypeptides in silk formulations (e.g., cosmetic and skin care formulations) that does not use harmful solvents and does not compromise the desirable properties of full-length silk proteins. [Means for solving the problem]

[0008] overview In some embodiments, provided herein is a method of producing a silk-based emulsion, the method comprising: mixing a composition comprising recombinant spider silk polypeptide powder and glycerol by applying pressure and shear forces to the composition, thereby converting the composition into an extrudate; suspending at least a portion of the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and mixing the aqueous extrudate suspension into an emulsion to form the silk-based emulsion.

[0009] In some embodiments, the extrudate is substantially homogeneous.In some embodiments, the silk-based emulsion is a cosmetic or skin care formulation.

[0010] In some embodiments, also provided herein is a method of producing a silk-based solid or gel, the method comprising: mixing a composition comprising recombinant spider silk polypeptide powder and glycerol by applying pressure and shear forces to the composition, thereby converting the composition into an extrudate; suspending the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and drying the aqueous extrudate suspension to form the silk-based solid or gel. In some embodiments, the method further comprises solidifying the aqueous extrudate suspension to form aggregated silk in the suspension.

[0011] In some embodiments, the silk-based solid or gel is a film. In some embodiments, the silk-based solid is a cosmetic or skin care formulation.

[0012] Also provided herein, according to some embodiments of the present invention, is a method of producing a silk-based formulation, the method comprising: providing a composition comprising silk protein and a plasticizer; applying pressure and shear forces to the composition, thereby converting the composition into an extrudate; and suspending the extrudate in an aqueous solvent to form an aqueous extrudate suspension.

[0013] In some embodiments, the method further comprises drying the aqueous extrudate suspension to form a silk-based solid or gel. In some embodiments, the method further comprises mixing the aqueous extrudate suspension into an emulsion to form the silk-based emulsion. In some embodiments, the method further comprises drying the silk-based emulsion to form a silk-based solid or gel. In some embodiments, the method further comprises adding a coagulant or additive to the silk-based solid or gel to form a firmer gel or solid. In some embodiments, the method further comprises coagulating the aqueous extrudate suspension to form coagulated silk in the suspension.

[0014] In some embodiments, the aqueous extrudate suspension comprises a gel phase, a colloid phase, and a solution phase. In some embodiments, the method further comprises separating the gel phase, the colloid phase, or the solution phase from the aqueous extrudate suspension. In some embodiments, the method further comprises drying the gel phase, the colloid phase, or the solution phase to form a silk-based solid or gel. In some embodiments, the method further comprises separating a mixture of the colloid phase and the solution phase from the aqueous extrudate suspension. In some embodiments, the method further comprises drying the mixture of the colloid phase and the solution phase to form a silk-based solid or gel.

[0015] In some embodiments, the silk is a recombinant spider silk. In some embodiments, the recombinant spider silk comprises a full-length protein. In some embodiments, the silk-based solid or gel is a skin care or cosmetic formulation. In some embodiments, the silk-based emulsion is a skin care or cosmetic formulation.

[0016] In some embodiments, the plasticizer is glycerin, in some embodiments, the aqueous solution is water, in some embodiments, the coagulant is methanol.

[0017] In some embodiments, the extrudate is in a flowable state.

[0018] In some embodiments, the silk-based solid or gel is non-toxic, hi some embodiments, the silk-based emulsion is non-toxic.

[0019] In some embodiments, the applied shear force is at least 1.5 Newton meters. In some embodiments, the applied pressure is at least 1 MPa.

[0020] In some embodiments, the method further comprises agitating the aqueous extrudate suspension.In some embodiments, the method further comprises applying heat to the aqueous extrudate suspension.

[0021] In some embodiments, the silk-based solid or gel is a film. In some embodiments, the film disperses when in contact with skin or water, or when gently rubbed. In some embodiments, the film disperses into liquid at temperatures below 37°C but above 23°C.

[0022] According to some embodiments, there is also provided herein a method of producing a silk-based gel, colloid, or solution, the method comprising: applying pressure and shear forces to a composition comprising silk protein and a plasticizer to mix the composition, thereby converting the composition into an extrudate; suspending the extrudate in an aqueous solvent to form an aqueous suspension extrudate; heating and / or stirring the aqueous suspension extrudate to form a gel phase, a colloid phase, and a solution phase; and separating the phases to produce the silk-based gel, colloid, or solution.

[0023] In some embodiments, provided herein are compositions comprising an extrudate comprising recombinant silk protein and a plasticizer, and the extrudate is suspended in an aqueous solution.

[0024] In some embodiments, the extrudate suspended in the aqueous solution forms a colloidal solution. In some embodiments, the extrudate is uniformly dispersed as particles in the aqueous solution. In some embodiments, the particles in the aqueous solution have a polydispersity index of 0.1 to 0.9. In some embodiments, the particles in the aqueous solution have a z-average of about 600 to 1,000 nm.

[0025] In some embodiments, the composition further comprises a coagulant.

[0026] In some embodiments, the plasticizer is glycerol.

[0027] In some embodiments, the composition is a film, hi some embodiments, the film is stable at room temperature and disperses upon contact with skin or water.

[0028] In some embodiments, the recombinant silk protein is a substantially full-length protein. In some embodiments, the recombinant silk protein is substantially free of aggregation in the composition. In some embodiments, the recombinant silk protein has a reduced, equivalent, or increased crystallinity compared to a powder form of the recombinant silk protein.

[0029] According to some embodiments, also provided herein is a spider silk cosmetic formulation or skin care product comprising an extrudate comprising silk proteins and a plasticizer, the extrudate being dispersed in an aqueous solvent or coagulant in a gel, colloid, or solution phase.

[0030] In some embodiments, the extrudate is dispersed in the aqueous solvent and the coagulant, hi some embodiments, the spider silk cosmetic formulation or skin care product is an emulsion or an aqueous solution.

[0031] According to some embodiments, also provided herein is a spider silk cosmetic formulation or skin care product comprising a solid or semi-solid material, the solid or semi-solid material comprising dispersed, non-aggregated recombinant silk protein and a plasticizer.

[0032] In some embodiments, the solid or semi-solid dissolves upon contact with the skin, hi some embodiments, the solid or semi-solid is a film. [The present invention 1001] 1. A method for producing a silk-based emulsion comprising: mixing a composition comprising recombinant spider silk polypeptide powder and glycerol by applying pressure and shear forces to said composition, thereby converting said composition into an extrudate; suspending at least a portion of the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and mixing the aqueous extrudate suspension into an emulsion to form the silk-based emulsion; The method comprising: [The present invention 1002] The process of claim 1001, wherein the extrudate is substantially homogeneous. [The present invention 1003] The method of claim 1001, wherein said silk-based emulsion is a cosmetic or skin care preparation. [The present invention 1004] 1. A method for producing a silk-based solid or gel, comprising: mixing a composition comprising recombinant spider silk polypeptide powder and glycerol by applying pressure and shear forces to said composition, thereby converting said composition into an extrudate; suspending the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and drying the aqueous extrudate suspension to form the silk-based solid or gel. The method comprising: [The present invention 1005] The method of claim 1004, further comprising coagulating said aqueous extrudate suspension to form coagulated silk in said suspension. [The present invention 1006] The method of claim 1004, wherein said silk-based solid or gel is a film. [The present invention 1007] The method of claim 1006, wherein said silk-based solid is a cosmetic or skin care preparation. [The present invention 1008] A method for producing a silk-based formulation, comprising: providing a composition comprising a silk protein and a plasticizer; applying pressure and shear forces to the composition, thereby converting the composition into an extrudate; and suspending the extrudate in an aqueous solvent to form an aqueous extrudate suspension. The method comprising: [The present invention 1009] The method of claim 1008, further comprising drying said aqueous extrudate suspension to form a silk-based solid or gel. [The present invention 1010] The method of claim 1008, further comprising mixing said aqueous extrudate suspension into an emulsion to form said silk-based emulsion. [The present invention 1011] The method of claim 1010, further comprising drying said silk-based emulsion to form a silk-based solid or gel. [The present invention 1012] The method of any one of claims 1009 to 1011, further comprising adding a coagulant or additive to said silk-based solid or gel to form a firmer gel or solid. [The present invention 1013] The method of any of claims 1008 to 1012, further comprising coagulating said aqueous extrudate suspension to form coagulated silk in said suspension. [The present invention 1014] The process of claim 1008, wherein the aqueous extrudate suspension comprises a gel phase, a colloidal phase, and a solution phase. [The present invention 1015] The process of claim 1014, further comprising separating said gel phase, said colloid phase, or said solution phase from said aqueous extrudate suspension. [The present invention 1016] The method of claim 1015, further comprising drying said gel phase, said colloid phase, or said solution phase to form a silk-based solid or gel. [The present invention 1017] The process of claim 1014, further comprising separating the mixture of said colloidal phase and said solution phase from said aqueous extrudate suspension. [The present invention 1018] The method of claim 1017, further comprising drying said mixture of said colloidal phase and said solution phase to form a silk-based solid or gel. [The present invention 1019] The method of claim 1014, wherein the silk is recombinant spider silk. [The present invention 1020] The method of any one of claims 1 to 19, wherein the recombinant spider silk comprises a full-length protein. [The present invention 1021] The method of any one of claims 1009 to 1011, wherein said silk-based solid or gel is a skin care preparation or a cosmetic preparation. [The present invention 1022] The method of claim 10, wherein said silk-based emulsion is a skin care preparation or a cosmetic preparation. [The present invention 1023] The method of claim 1008, wherein the plasticizer is glycerin. [The present invention 1024] The method of claim 1008, wherein the extrudate is in a flowable state. [The present invention 1025] The method of claim 1008, wherein the aqueous solution is water. [The present invention 1026] The method of claim 1012, wherein the coagulant is methanol. [The present invention 1027] The method of any one of claims 1009 to 1011, wherein said silk-based solid or gel is non-toxic. [The present invention 1028] The method of claim 10, wherein said silk-based emulsion is non-toxic. [The present invention 1029] The method of claim 1008, wherein the applied shear force is at least 1.5 Newton meters. [The present invention 1030] The method of claim 1008, wherein the applied pressure is at least 1 MPa. [The present invention 1031] The process of claim 1008, further comprising agitating said aqueous extrudate suspension. [The present invention 1032] The process of claim 1008, further comprising heating said aqueous extrudate suspension. [The present invention 1033] The method of any one of claims 1009 to 1011, wherein the silk-based solid or gel is a film. [The present invention 1034] The method of claim 1033, wherein the film disperses upon contact with skin or water, or upon gentle rubbing. [The present invention 1035] The method of claim 1033, wherein the film disperses in a liquid at a temperature below 37°C but above 23°C. [The present invention 1036] 1. A method for producing a silk-based gel, colloid, or solution, comprising: mixing the composition comprising silk protein and a plasticizer by applying pressure and shear forces to said composition, thereby converting said composition into an extrudate; suspending the extrudate in an aqueous solvent to form an aqueous suspension extrudate; heating and / or stirring the aqueous suspension extrudate to form a gel phase, a colloid phase, and a solution phase; and Separating the phases to produce a silk-based gel, colloid, or solution. The method comprising: [The present invention 1037] 1. A composition comprising an extrudate comprising recombinant silk protein and a plasticizer, wherein the extrudate is suspended in an aqueous solution. [The present invention 1038] The composition of claim 1037, wherein the extrudates are uniformly dispersed as particles in the aqueous solution. [The present invention 1039] The composition of claim 1038, wherein said particles in said aqueous solution have a polydispersity index of 0.1 to 0.9. [The present invention 1040] 1038. The composition of matter of the present invention, wherein said particles in said aqueous solution have a z-average of about 600 to 1,000 nm. [The present invention 1041] The composition of claim 1037, wherein the extrudate suspended in the aqueous solution forms a colloidal solution. [The present invention 1042] The composition of claim 1037, further comprising a coagulant. [The present invention 1043] The composition of the present invention 1037, wherein the plasticizer is glycerol. [The present invention 1044] The composition of the present invention 1037, which is a film. [The present invention 1045] The composition of the present invention 1037, wherein the film is stable at room temperature and disperses upon contact with skin or water. [The present invention 1046] The composition of claim 1037, wherein the recombinant silk protein is a substantially full-length protein. [The present invention 1047] The composition of claim 1037, wherein the recombinant silk protein is substantially not aggregated in the composition. [The present invention 1048] The composition of the present invention 1037, wherein the recombinant silk protein has a reduced, equivalent, or increased crystallinity compared to a powder form of the recombinant silk protein. [The present invention 1049] 1. A spider silk cosmetic or skin care product comprising an extrudate comprising silk proteins and a plasticizer, said extrudate being dispersed in an aqueous solvent or coagulant in a gel, colloid, or solution phase. [The present invention 1050] The composition of claim 1049, wherein the extrudate is dispersed in the aqueous solvent and the coagulant. [The present invention 1051] The composition of claim 1049, wherein said spider silk cosmetic or skin care product is an emulsion or aqueous solution. [The present invention 1052] 1. A spider silk cosmetic or skin care product, comprising a solid or semi-solid material, said solid or semi-solid material comprising dispersed, non-aggregated recombinant silk protein and a plasticizer. [The present invention 1053] The composition of claim 1052, wherein said solid or semi-solid dissolves upon contact with the skin. [The present invention 1054] The composition of claim 1053, wherein the solid or semi-solid is a film. [Brief description of the drawings]

[0033] The above and other objects, features and advantages will become apparent from the following description of specific embodiments of the invention, which are illustrated in the accompanying drawings.

[0034] [Figure 1] 1 shows size exclusion chromatography data for P49W21G30 melt compositions extruded under selected thermal and RPM conditions, according to various embodiments of the present invention.

[0035] [Diagram 2] 1 shows size exclusion chromatography data for P65W20G15 melt compositions extruded under selected thermal and RPM conditions according to various embodiments of the present invention.

[0036] [Diagram 3]1 shows size exclusion chromatography data for P71W19G10 melt compositions extruded under selected thermal and RPM conditions, according to various embodiments of the present invention.

[0037] [Figure 4] 1 shows a chart of moisture loss during extrusion of P49W21G30 melt compositions extruded under selected thermal and RPM conditions as measured by thermogravimetric analysis (TGA) in accordance with various embodiments of the present invention. The data shows the percent moisture content of the starting pellets before extrusion and the extruded samples under the selected conditions after extrusion.

[0038] [Diagram 5] 1 shows a chart of moisture loss during extrusion of P65W20G15 melt compositions extruded under selected thermal and RPM conditions as measured by thermogravimetric analysis (TGA) in accordance with various embodiments of the present invention. The data shows the percent moisture content of the starting pellets before extrusion and the extruded samples under the selected conditions after extrusion.

[0039] [Figure 6] 1 shows a chart of moisture loss during extrusion of P71W19G10 melt compositions extruded under selected thermal and RPM conditions as measured by thermogravimetric analysis (TGA) in accordance with various embodiments of the present invention. The data shows the percent moisture content of the starting powder before extrusion and the sample extruded under the selected conditions after extrusion.

[0040] [Figure 7]

[0023] Figure 1 shows the beta sheet content of P49W21G30 samples extruded under selected thermal and RPM conditions as measured by Fourier Transform Infrared Spectroscopy (FTIR). Samples were compared to reference controls of starting protein powder and starting pellets.

[0041] [Figure 8]Figure 1 shows the beta-sheet content of P65W20G15 samples extruded under selected thermal and RPM conditions as measured by Fourier Transform Infrared Spectroscopy (FTIR) and compared to the starting protein powder and starting pellet reference controls.

[0042] [Figure 9]

[0023] Figure 1 shows the beta sheet content of P71W19G10 samples extruded under selected thermal and RPM conditions as measured by Fourier Transform Infrared Spectroscopy (FTIR). Samples were compared to reference controls of starting protein powder and starting pellets.

[0043] [Figure 10] Shown are images of selected extrusion products produced at 10, 100, 200 or 300 RPM at 20° C. captured using a polarized light microscope.

[0044] [Figure 11] Shown are images of selected extrusion products produced at 95° C. and 10, 100, 200, or 300 RPM captured using polarized light microscopy.

[0045] [Figure 12] 1 shows a chart of glycerol loss measured by HPLC during extrusion of P49W21G30 extrudates extruded under selected thermal and RPM conditions according to various embodiments of the present invention. The data shows the glycerol content (%) of the starting powder or pellets for pre-extrusion and post-extrusion samples under selected conditions.

[0046] [Figure 13] 1 shows a chart of glycerol loss measured by HPLC during extrusion of P65W20G15 extrudates extruded under selected thermal and RPM conditions according to various embodiments of the present invention. The data shows the glycerol content (%) of the starting powder or pellets for pre-extrusion and post-extrusion samples under selected conditions.

[0047] [Figure 14] 1 shows a chart of glycerol loss measured by HPLC during extrusion of P71W19G10 extrudates extruded under selected thermal and RPM conditions according to various embodiments of the present invention. The data shows the glycerol content (%) of the starting powder or pellets for pre-extrusion and post-extrusion samples under selected conditions.

[0048] [Figure 15] Shown are micrographs and magnified images (inset) of silk / glycerin prepared using an Xplore MC15 conical twin screw extruder (Xplore TCE) with 10% silk, 17% silk, or 25% silk in glycerin for the periods and temperatures indicated. For reference, silk powder not dissolved in glycerin is shown.

[0049] [Figure 16] Optical microscope images of extrudates cycled in an Xplore TSE extruder at 90° C. for 30 seconds, 4 minutes, 5 minutes, 10 minutes, 20 minutes, 0.5 hours, 1 hour, and 1.5 hours are shown.

[0050] [Figure 17] Optical microscope images of the extrudate, the extrudate resuspended in water at various concentrations, and the extrudate resuspended in water after stirring at room temperature or at 90° C. are shown.

[0051] FIG. 17 shows optical microscope images of the extrudate, the extrudate resuspended in water at various concentrations, and the extrudate resuspended in water after stirring at room temperature or at 90° C.

[0052] [Figure 18]Shown are photographs and micrographs of i) a solution of extrudate suspended in water prior to phase separation, ii) a gel pellet phase, a colloidal supernatant (i.e., "colloidal super"), and iii) a colloidal and solution phase separated from the colloidal supernatant. Also shown are dried films produced from i) the extrudate suspended in water prior to phase separation, ii) the gel pellet, iii) the colloidal supernatant, and iv) the solution phase.

[0053] [Figure 19] 1 illustrates a process for creating a silk-glycerol emulsion film and applying the film to the skin of a test subject according to an embodiment of the present invention.

[0054] [Figure 20] 1 illustrates a process for creating a silk-glycerol emulsion freeze-dried film and applying the film to the skin of a test subject according to an embodiment of the present invention.

[0055] [Figure 21] The process of making and drying i) a suspension of silk-glycerin extrudate and ii) a suspension of silk-glycerin slurry (non-extrudate) is shown, along with the drying results of each suspension and representative film-forming properties of each.

[0056] [Figure 22] The process of preparation and drying of i) emulsions containing silk-glycerin extrudates and ii) emulsions containing silk-glycerin slurries (non-extrudates) is shown, along with the drying results of each suspension and representative film-forming properties of each.

[0057] [Diagram 23] Shown are photographs and micrographs of i) aqueous resuspended extrudate diluted 5-fold with water, and ii) aqueous resuspended extrudate diluted 5-fold with methanol.

[0058] [Figure 24] Silk-glycerin extrudate dry films are shown i) without exposure to methanol and ii) after exposure to methanol on the skin (left), and the same film composition was also rubbed onto the skin (right).

[0059] [Figure 25A] FIG. 1 shows FTIR spectra analyzed for beta-sheet content of selected silk extrudate and non-extrudate compositions described herein. [Figure 25B] Quantitation of the relative beta-sheet content in these compositions, as determined from FTIR spectra, is shown. [Figure 25C] Quantification of the amino acid content relative to glycerin in these compositions as determined from FTIR spectra is shown.

[0060] [Figure 26] The viscosity of dry suspensions containing 20%, 15%, 10% and 5% of the extrudate suspended in water and the respective FTIR peaks corresponding to the beta-sheet content are shown.

[0061] [Figure 27] 1 shows a graph of protein concentration (wt%) of aggregates, full length, and low molecular weight proteins measured by size exclusion chromatography for powder, powder supernatant, extrudate, and extrudate supernatant.

[0062] [Figure 28] FIG. 1 shows the particle size distribution of the extrudate supernatant measured with a Malvin instrument, Zetasizer Nano.

[0063] [Figure 29] 4 shows images of 5% silk powder mixture (left) and 5% silk extrudate supernatant (right) solutions obtained after 24 hours of incubation at 4° C.

[0064] [Diagram 30]1 shows plots of transepidermal water loss measured on skin moisture before tape removal (baseline), after tape removal (post-removal), and after 30 minutes and 2 hours of application of i) untreated, ii) water containing 15% glycerin (vehicle control), and iii) 5% silk protein extrudate mixture (5% extrudate) on tape-removed skin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0065] Detailed Description Details of various embodiments of the present invention are described as follows. Other features, objects, and advantages of the present invention will become apparent from this description. Unless otherwise defined herein, scientific and technical terms used in connection with the present invention shall have the meanings commonly understood by those skilled in the art. Furthermore, unless otherwise required by the context, singular terms include plurals and plural terms include the singular. The terms "a" and "an" include plural referents unless otherwise required by the context. Generally, the terminology used in connection with and techniques relating to biochemistry, enzymology, molecular cell biology, microbiology, genetics, and protein and nucleic acid chemistry, and hybridization described herein are those commonly used techniques well known in the art.

[0066] definition Unless otherwise indicated, the following terms shall be understood to have the following meanings:

[0067] The term "stability" as used herein with respect to silk proteins refers to the ability of a product to not undergo gelation, discoloration, or turbidity due to self-aggregation of silk proteins. For example, U.S. Patent Publication No. 2015 / 0079012 (Wray et al.) relates to the use of moisturizers containing glycerol to enhance the storage stability of skin care products containing full-length silk fibroin. U.S. Patent Publication No. 9,187,538 relates to skin care formulations containing full-length silk fibroin that exhibit storage stability for up to 10 days. Both of these documents are incorporated herein by reference in their entirety.

[0068] The term "polynucleotide" or "nucleic acid molecule" refers to a polymeric form of nucleotides having a length of at least 10 bases. Such terms include DNA molecules (e.g., cDNA or genomic DNA or synthetic DNA) and RNA molecules (e.g., mRNA or synthetic RNA), as well as analogs of DNA or RNA that contain non-natural nucleotide analogs, non-natural internucleoside linkages, or both. Nucleic acids can be in any topological conformation. For example, nucleic acids can be in single-stranded, double-stranded, triple-stranded, quadruplexed, partially double-stranded, branched, hairpinned, circular, or padlocked conformation.

[0069] Unless otherwise indicated, as an example for any sequence described herein in the general format of "SEQ ID NO:", a "nucleic acid comprising SEQ ID NO: 1" refers to a nucleic acid having, at least in part, (i) the sequence set forth in SEQ ID NO: 1, or (ii) a sequence complementary to SEQ ID NO: 1. The alternative is dictated by the context. For example, if the nucleic acid is being used as a probe, the alternative is dictated by the requirement that the probe be complementary to the desired target.

[0070] "Isolated" RNA, DNA, or mixed polymers are those that are substantially separated from other cellular components which naturally accompany the natural polynucleotides in the natural host cell to which they belong, such as naturally associated ribosomes, polymerases, and genomic sequences.

[0071] An "isolated" organic molecule (e.g., silk protein) is one that has been substantially separated from cellular components (membrane lipids, chromosomes, proteins) of the host cell from which it is derived or from the medium in which the host cell is cultured. The term does not require that the biomolecule be separated from all other chemicals, although certain isolated biomolecules may be purified to near homogeneity.

[0072] The term "recombinant" refers to a biological molecule, such as a gene or protein, that is (1) removed from its natural environment, (2) not associated with all or a portion of a polynucleotide with which the gene is found in nature, (3) operably linked to a polynucleotide with which it is not linked in nature, or (4) not occurring in nature. The term "recombinant" may be used in reference to cloned DNA isolates, chemically synthesized polynucleotide analogs, or polynucleotide analogs biologically synthesized in heterologous systems, as well as proteins and / or mRNAs encoded by such nucleic acids.

[0073] An endogenous nucleic acid sequence is considered "recombinant" herein when a heterologous sequence is placed adjacent to an endogenous nucleic acid sequence of an organism's genome such that the expression of the endogenous nucleic acid sequence (or the protein product that the sequence encodes) is altered. In this case, the heterologous sequence is a sequence that is not naturally adjacent to the endogenous nucleic acid sequence, regardless of whether the heterologous sequence is itself endogenous (from the same host cell, or its progeny) or exogenous (from a different host cell, or its progeny). As an example, a promoter sequence replaces (e.g., by homologous recombination) the native promoter of a gene present in the genome of a host cell, thereby altering the expression pattern of the gene. The gene is now considered "recombinant" because it has been separated from at least some of the sequences that naturally flank it.

[0074] A nucleic acid is also considered to be "recombinant" if it contains any modification relative to the corresponding nucleic acid in a genome that does not occur naturally. For example, an endogenous coding sequence is considered to be "recombinant" if it has an insertion, deletion, or point mutation that has been artificially introduced, such as by human intervention. "Recombinant nucleic acid" also includes a nucleic acid integrated into a host cell chromosome at a heterologous site, and a nucleic acid construct that exists as an episome.

[0075] As used herein, the term "peptide" refers to short polypeptides, e.g., generally less than about 50 amino acids in length, more generally less than about 30 amino acids in length. As used herein, the term includes analogs and mimetics that mimic structure-function and thereby biological function.

[0076] The term "polypeptide" includes both naturally occurring and non-naturally occurring proteins, as well as fragments, variants, derivatives, and analogs thereof. A polypeptide may be monomeric or polymeric. Furthermore, a polypeptide may contain multiple distinct domains, each having one or more distinct activities.

[0077] The term "isolated protein" or "isolated polypeptide" refers to, in terms of its origin or source of derivation, (1) a protein or polypeptide that is not associated with naturally associated components that accompany it in its natural state; (2) a protein or polypeptide that exists in a purity not found in nature, where the purity can be determined with respect to the presence of other cellular material (e.g., free of other proteins from the same species); (3) a protein or polypeptide expressed by cells from a different species; or (4) a protein or polypeptide that does not occur in nature (e.g., is a fragment of a naturally occurring polypeptide or contains amino acid analogs or derivatives not found in nature, or bonds other than standard peptide bonds). Thus, chemically synthesized polypeptides or polypeptides synthesized in a cellular system different from the cells from which they naturally originate are "isolated" from their naturally associated components. Polypeptides or proteins can be isolated to be substantially free of naturally associated components using protein purification techniques well known in the art. When so defined, "isolated" does not necessarily require that the proteins, polypeptides, peptides, or oligopeptides so described have been physically removed from their natural environment.

[0078] The term "polypeptide fragment" refers to a polypeptide having a deletion compared to the full-length polypeptide, e.g., an amino-terminal and / or carboxy-terminal deletion. In a preferred embodiment, a polypeptide fragment is a contiguous sequence in which the amino acid sequence of the fragment is identical to the corresponding positions in the naturally occurring sequence. A fragment is generally at least 5, 6, 7, 8, 9 or 10 amino acids in length, preferably at least 12, 14, 16 or 18 amino acids in length, more preferably at least 20 amino acids in length, more preferably at least 25, 30, 35, 40 or 45 amino acids in length, even more preferably at least 50 or 60 amino acids in length, and even more preferably at least 70 amino acids in length.

[0079] A protein has "homology" or is "homologous" to a second protein if the nucleic acid sequence encoding the protein has a similar sequence to the nucleic acid sequence encoding the second protein. Alternatively, a protein has homology to a second protein if the two proteins have "similar" amino acid sequences. (Thus, the term "homologous proteins" is defined to mean that two proteins have similar amino acid sequences). As used herein, homology between two amino acid sequence regions (especially with respect to predicted structural similarities) is interpreted to mean similarity in function.

[0080] When "homologous" is used in reference to proteins or peptides, it is recognized that residue positions that are not identical often differ by conservative amino acid substitutions. A "conservative amino acid substitution" is one in which an amino acid residue is replaced with another amino acid residue having a side chain (R group) with similar chemical properties (e.g., charge or hydrophobicity). Generally, conservative amino acid substitutions do not substantially change the functional properties of a protein. When two or more amino acid sequences differ from each other by conservative substitutions, the percent sequence identity or degree of homology may be adjusted upwards to correct for the conservative nature of the substitution. Means for making such adjustments are well known to those of skill in the art. See, e.g., Pearson, 1994, Methods Mol. Biol. 24:307-31 and 25:365-89, incorporated herein by reference.

[0081] The twenty conventional amino acids and their abbreviations follow convention. See Immunology-A Synthesis (Golub and Gren eds., Sinauer Associates, Sunderland, Mass., 2001), incorporated herein by reference. nd ed. 1991). Stereoisomers of the twenty conventional amino acids (e.g., D-amino acids), non-naturally occurring amino acids, such as α-,α-disubstituted amino acids, N-alkylamino acids, and other non-conventional amino acids may also be suitable components of the polypeptides of the invention. Examples of non-conventional amino acids include 4-hydroxyproline, γ-carboxyglutamic acid, ε-N,N,N-trimethyllysine, ε-N-acetyllysine, O-phosphoserine, N-acetylserine, N-formylmethionine, 3-methylhistidine, 5-hydroxylysine, N-methylarginine, and other similar amino acids and imino acids (e.g., 4-hydroxyproline). In the polypeptide notation used herein, the left-hand end corresponds to the amino terminus and the right-hand end corresponds to the carboxy terminus, in accordance with standard usage and convention.

[0082] Each of the following six groups contains amino acids that are conservative substitutions for one another: 1) serine (S), threonine (T); 2) aspartic acid (D), glutamic acid (E); 3) asparagine (N), glutamine (Q); 4) arginine (R), lysine (K); 5) isoleucine (I), leucine (L), methionine (M), alanine (A), valine (V), and 6) phenylalanine (F), tyrosine (Y), tryptophan (W).

[0083] Sequence homology of polypeptides, sometimes referred to as percent sequence identity, is typically measured using sequence analysis software. See, for example, Sequence Analysis Software Package of the Genetics Computer Group (GCG), University of Wisconsin Biotechnology Center, 910 University Avenue, Madison, Wis. 53705. Protein analysis software matches similar sequences using homology measures assigned to various substitutions, deletions, and other modifications, including conservative amino acid substitutions. For example, GCG comes with programs such as "Gap" and "Bestfit," which can be used with default parameters to determine sequence homology or sequence identity between closely related polypeptides, such as homologous polypeptides from different species of organisms, or between a wild-type protein and its mutant protein. See, for example, GCG version 6.1.

[0084] A useful algorithm for comparing a particular polypeptide sequence to a database containing a large number of sequences from different organisms is the computer program BLAST (Altschul et al., J. Mol. Biol. 215:403-410 (1990); Gish and States, Nature Genet. 3:266-272 (1993); Madden et al., Meth. Enzymol. 266:131-141 (1996); Altschul et al., Nucleic Acids Res. 25:3389-3402 (1997); Zhang and Madden, Genome Res. 7:649-656 (1997)), in particular blastp or tblastn (Altschul et al., Nucleic Acids Res. 25:3389-3402 (1997)).

[0085] Preferred parameters for BLASTp are expectation: 10 (default); filter: seg (default); gap opening cost: 11 (default); gap extension cost: 1 (default); maximum alignments: 100 (default); string size: 11 (default); number of matches displayed: 100 (default); penalty matrix: BLOWSUM62.

[0086] Preferred parameters for BLASTp are expectation: 10 (default); filter: seg (default); cost of opening gap: 11 (default); cost of extending gap: 1 (default); maximum alignment: 100 (default); string size: 11 (default); number of results displayed: 100 (default); penalty matrix: BLOWSUM62. The length of polypeptide sequences to be compared for homology will generally be at least about 16 amino acid residues, usually at least about 20 residues, more usually at least about 24 residues, usually at least about 28 residues, and preferably more than about 35 residues. When searching a database containing sequences from many different organisms, it is preferred to compare amino acid sequences. Database searches using amino acid sequences can be measured by algorithms known in the art other than blastp. For example, polypeptide sequences can be compared using FASTA, a program in GCG version 6.1. FASTA provides alignments and percent sequence identity of the regions of best overlap between the query and search sequences. Pearson, Methods Enzymol. 183:63-98 (1990), which is incorporated herein by reference. For example, percent sequence identity between amino acid sequences can be determined using FASTA, provided in GCG version 6.1, which is incorporated herein by reference, with its default parameters (string size of 2 and scoring matrix PAM250).

[0087] It should be understood that throughout this specification and the claims, the word "comprise" or variations such as "comprises" or "comprising" are meant to mean the inclusion of a stated integer or group of integers, but not the exclusion of any other integer or group of integers.

[0088] As used herein, the term "glass transition" refers to the transition of a substance or composition from a hard, rigid, or "glassy" state to a more flexible, "rubbery" or "viscous" state.

[0089] As used herein, the term "glass transition temperature" refers to the temperature at which a material or composition undergoes a glass transition.

[0090] As used herein, the term "melt transition" refers to the transition of a material or composition from a rubbery state to a less ordered liquid phase or flowable state.

[0091] As used herein, the term "melting temperature" refers to the temperature range at which a material undergoes a melting transition.

[0092] As used herein, the term "plasticizer" refers to any molecule that interacts with a polypeptide sequence to prevent the polypeptide sequence from forming tertiary structures and bonds and / or to increase the mobility of the polypeptide sequence.

[0093] As used herein, the term "flowable state" refers to a composition that has substantially the same properties as a liquid (ie, has transitioned from a rubbery state further into a liquid state).

[0094] Exemplary methods and materials are described below, although methods and materials similar or equivalent to those described herein can also be used in practicing the present invention and will be apparent to those skilled in the art. All publications and other references mentioned herein are incorporated by reference in their entirety. In case of conflict, the present specification, including definitions, will control. The materials, methods, and examples are intended to be illustrative only and not limiting.

[0095] Recombinant silk proteins This disclosure describes embodiments of the invention that include fibers synthesized from synthetic proteinaceous copolymers (i.e., recombinant polypeptides). Suitable proteinaceous copolymers are described in U.S. Patent Publication Nos. 2016 / 0222174, published Aug. 45, 2016, 2018 / 0111970, published Apr. 26, 2018, and 2018 / 0057548, published Mar. 1, 2018, the entire contents of each of which are incorporated herein by reference.

[0096] In some embodiments, synthetic protein copolymers are created from silk-like polypeptide sequences. In some embodiments, the silk-like polypeptide sequences are 1) block copolymer polypeptide compositions produced by mixing and matching repeat domains from silk polypeptide sequences, and / or 2) recombinant expression of block copolymer polypeptides large enough (about 40 kDa) to be secreted by industrially scalable microorganisms to form useful molded body compositions. Large (about 40 kDa to about 100 kDa) block copolymer polypeptides engineered with silk repeat domain fragments, including sequences from nearly all of the published amino acid sequences of spider silk polypeptides, can be expressed in the engineered microorganisms described herein. In some embodiments, silk polypeptide sequences are designed to produce highly expressed and highly secreted polypeptides capable of forming molded bodies.

[0097] In some embodiments, block copolymers are engineered to combine and mix silk polypeptide domains across the entire silk polypeptide sequence space. In some embodiments, block copolymers are produced by expression and secretion in scalable organisms (e.g., yeast, fungi, and gram-positive bacteria). In some embodiments, block copolymer polypeptides include zero or more N-terminal domains (NTDs), one or more repeat domains (REPs), and zero or more C-terminal domains (CTDs). In some aspects of the embodiments, the block copolymer polypeptides are single-chain polypeptides of more than 100 amino acids. In some embodiments, the block copolymer polypeptide comprises a domain that is at least 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or 99% identical to the sequence of a block copolymer polypeptide disclosed in International Publication No. WO / 2015 / 042164, "Methods and Compositions for Synthesizing Improved Silk Fibers," the entire contents of which are incorporated herein by reference.

[0098] Several species of natural spider silk have been identified so far, and the various mechanical properties of naturally spun silk are thought to be closely related to the molecular composition of the silk. See, e.g., Garb, J. E., et al., Untangling spider silk evolution with spidroin terminal domains, BMC Evol. Biol., 10:243 (2010); Bittencourt, D., et al., Protein families, natural history and biotechnological aspects of spider silk, Genet. Mol. Res., 11:3 (2012); Rising, A., et al., Spider silk proteins: recent advances in recombinant production, structure-function relationships and biomedical applications, Cell. Mol. Life Sci., 68:2, pg. 169-184 (2011); and Humenik, M., et al., Spider silk: understanding the structure-function relationship of a natural fiber, Prog. Mol. Biol. Transl. Sci., 103, pg. 131-85 (2011). For example:

[0099] Tufted (AcSp) silks tend to be tough, combining moderately high strength with moderately high stretchability. AcSp silks are characterized by large block ("repeat aggregate") sizes that often incorporate polyserine and GPX motifs. Tubular (TuSp, or cylindrical) silks tend to be large in diameter, moderate in strength, and high in stretchability. TuSp silks are characterized by their polyserine and polythreonine content, as well as short polyalanine sequences. Large ampullate (MaSp) silks tend to be high in strength and moderate in stretchability. MaSp silks are of two subtypes, MaSp1 and MaSp2. MaSp1 silks are generally less stretchable than MaSp2 silks, and are characterized by polyalanine, GX, and GGX motifs. MaSp2 silks are characterized by polyalanine, GGX, and GPX motifs. MiSp silks tend to have moderate strength and moderate stretchability. MiSp silks are characterized by GGX, GA, and polyA motifs and often contain a spacer element of about 100 amino acids. Flagelliform (Flag) silks tend to have very high stretchability and moderate strength. Flag silks are usually characterized by GPG, GGX, and a short spacer motif.

[0100] The properties of each silk species may vary from species to species, and spiders with different lifestyles (e.g. stationary web-weaving spiders vs. wandering feeding spiders) or evolutionarily older spiders may produce silks that differ from the above description (for a description of spider diversity and classification see Hormiga, G., and Griswold, C.E., Systematics, phylogeny, and evolution of orb-weaving spiders, Annu. Rev. Entomol. 59, pg. 487-512 (2014); and Blackedge, T.A. et al., Reconstructing web evolution and spider diversification in the molecular era, Proc. Natl. Acad. Sci. USA, 106:13, pg. 5229-5234 (2009)). However, synthetic block copolymer polypeptides having sequence similarity and / or amino acid composition similarity to the repeating domains of natural silk proteins can be used to produce consistent bodies on a commercial scale that reproduce the properties of corresponding bodies made from natural silk polypeptides.

[0101] In some embodiments, a list of putative silk sequences can be collected by searching GenBank for related terms such as "spidroin", "fibroin", "MaSp", etc., and these sequences can be pooled together with additional sequences obtained by independent sequencing. These sequences are then translated into amino acids, filtered for duplicate entries, and manually divided into their respective domains (NTD, REP, CTD). In some embodiments, the candidate amino acid sequences are reverse translated into DNA sequences optimized for expression in Pichia (Komagataella) pastoris. The DNA sequences are cloned into respective expression vectors and transformed into Pichia (Komagataella) pastoris. In some embodiments, the various silk domains that show successful expression and secretion are then assembled in a combinatorial manner to construct silk molecules capable of forming molded bodies.

[0102] Silk polypeptides characteristically consist of a repetitive domain (REP) flanked by non-repetitive regions (e.g., C-terminal and N-terminal domains). In one embodiment, both the C-terminal and N-terminal domains are 75-350 amino acids in length. The repetitive domains exhibit a hierarchical structure, as shown in FIG. 1. The repetitive domains contain a series of blocks (also known as repeat units), which sometimes repeat perfectly and sometimes imperfectly throughout the repetitive domain of silk (forming quasi-repetitive domains). The length and composition of the blocks vary between different silk species and between different species. Table 1A lists the block sequences of selected species and silk species, with further examples described in Rising, A. et al., Spider silk proteins: recent advances in recombinant production, structure-function relationships and biomedical applications, Cell Mol. Life Sci., 68:2, pg 169-184 (2011); and Gatesy, J. et al., Extreme diversity, conservation, and convergence of spider silk fibroin sequences, Science, 291:5513, pg.2603-2605 (2001). In some cases, the blocks are usually arranged in a pattern and may form larger macrorepeats that occur multiple times (usually 2-8 times) in the repetitive domain of the silk sequence. Blocks that are repeated inside the repetitive domain or macrorepeat may be separated by spacing elements from macrorepeats that are repeated within the repetitive domain. In some embodiments, the block sequence comprises a glycine-rich region followed by a polyA region. In some embodiments, a short (about 1-10) amino acid motif occurs multiple times within a block.For the purposes of the present invention, blocks from different natural silk polypeptides can be selected regardless of circular permutation (i.e., if the identified blocks are otherwise similar between silk polypeptides, they may not be aligned due to circular permutation). Thus, for example, the "block" SGAGG (SEQ ID NO: 35) is, for the purposes of the present invention, identical to GSGAG (SEQ ID NO: 36) and identical to GGSGA (SEQ ID NO: 37); they are just circular permutations of each other. The particular permutation selected for a given silk sequence can be determined, among other things, by convenience (usually starting with G). Silk sequences obtained from the NCBI database can be divided into blocks and non-repetitive regions. [Table 1A] TIFF0007640107000002.tif151163TIFF0007640107000003.tif164163TIFF0007640107000004.tif20216 3TIFF0007640107000005.tif207161TIFF0007640107000006.tif186163TIFF0007640107000007.tif52163

[0103] According to certain embodiments of the invention, fiber-forming block copolymer polypeptides derived from blocks and / or macro-repeat domains are described in International Publication No. WO / 2015 / 042164, which is incorporated herein by reference. Natural silk sequences obtained from protein databases such as GenBank or by de novo sequencing have domains (N-terminal, repeat and C-terminal) broken down. The N-terminal and C-terminal domain sequences selected for post-synthetic assembly to construct fibers or bodies include the natural amino acid sequence information and other modifications described herein. The repeat domains are broken down into repeat sequences that typically contain 1-8 representative blocks, depending on the type of silk, that capture the important amino acid information while reducing the size of the DNA encoding the amino acids to easily synthesizable fragments. In some embodiments, a properly formed block copolymer polypeptide comprises at least one repeat domain that includes at least one repeat sequence, optionally flanked by an N-terminal domain and / or a C-terminal domain.

[0104] In some embodiments, the repeat domain comprises at least one repeat sequence. In some embodiments, the repeat sequence is 150-300 amino acid residues. In some embodiments, the repeat sequence comprises multiple blocks. In some embodiments, the repeat sequence comprises multiple macrorepeats. In some embodiments, the blocks or macrorepeats are divided throughout the multiple repeat sequences.

[0105] In some embodiments, the repeat sequence cannot start with glycine and end with phenylalanine (F), tyrosine (Y), tryptophan (W), cysteine ​​(C), histidine (H), asparagine (N), methionine (M), or aspartic acid (D) to meet DNA assembly requirements. In some embodiments, some repeat sequences can be altered compared to the native sequence. In some embodiments, the repeat sequence can be altered, such as by adding a serine to the C-terminus of the polypeptide (to avoid termination at F, Y, W, C, H, N, M, or D). In some embodiments, the repeat sequence can be modified by filling incomplete blocks with homologous sequences from another block. In some embodiments, the repeat sequence can be modified by rearranging the order of the blocks or macrorepeats.

[0106] In some embodiments, unique N-terminal and C-terminal domains can be selected for synthesis. In some embodiments, N-terminal domains can be created by removing leading signal sequences, for example, as identified in SignalP (Peterson, TN, et. Al., SignalP 4.0: discriminating signal peptides from transmembrane regions, Nat. Methods, 8:10, pg. 785-786 (2011)).

[0107] In some embodiments, the N-terminal domain sequence, the repeat sequence, or the C-terminal domain sequence is selected from the group consisting of Agelenopsis aperta, Aliatypus gulosus, Aphonopelma seemanni, Aptostichus sp. AS217, Aptostichus sp. AS220, Araneus diadematus, Araneus gemmoides, Araneus ventricosus, Argiope amoena, Argiope argentata, Argiope bruennichi, Argiope trifasciata, Atypoides riversi, Avicularia juruensis, Bothriocyrtum californicum, Deinopis spinosa, Diguetia canities, Dolomedes tenebrosus, Euagrus chisoseus, Euprosthenops australis, Gasteracantha mammosa, Hypochilus thorelli, Kukulcania hibernalis, Latrodectus hesperus, Megahexura fulva, Metepeira grandiosa, Nephila antipodiana, Nephila clavata, Nephilaclavipes, Nephila madagascariensis, Nephila pilipes, Nephilengys cruentata, Parawixia bistriata, Peucetia viridans, Plectreurys tristis, Poecilotheria regalis, Tetragnatha kauaiensis, or Uloborus diversus.

[0108] In some embodiments, the silk polypeptide nucleotide coding sequence can be operably linked to an alpha mating factor nucleotide coding sequence. In some embodiments, the silk polypeptide nucleotide coding sequence can be operably linked to another endogenous or heterologous secretion signal coding sequence. In some embodiments, the silk polypeptide nucleotide coding sequence can be operably linked to a 3X FLAG nucleotide coding sequence. In some embodiments, the silk polypeptide nucleotide coding sequence can be operably linked to a 3X FLAG nucleotide coding sequence. In some embodiments, the silk polypeptide nucleotide coding sequence can be operably linked to an alpha mating factor nucleotide coding sequence. (SEQ ID NO:38) The affinity tag is operably linked to another affinity tag such as

[0109] In some embodiments, the recombinant spider silk polypeptide is based on a recombinant spider silk protein fragment sequence from MaSp2, such as from the species Argiope bruennichi. In some embodiments, the synthetic fibers include protein molecules that include 2-20 repeat units, each repeat unit having a molecular weight greater than about 20 kDa. Within each repeat unit of the copolymer, there are more than about 60 amino acid residues, often in the range of 60-100 amino acids, organized into several "quasi-repeat units." In some embodiments, the repeat units of the polypeptides described herein have at least 95% sequence identity to the MaSp2 drugline silk protein sequence.

[0110] Repeat units of proteinaceous block copolymers that form fibers with good mechanical properties can be synthesized using parts of silk polypeptides. These polypeptide repeat units include alanine-rich and glycine-rich regions and are 150 amino acids or more in length. Some exemplary sequences that can be used as repeats in proteinaceous block copolymers of the present disclosure are provided in co-owned PCT publication WO2015 / 042164, the entire contents of which are incorporated herein by reference, and have been demonstrated to be expressed using Pichia expression systems.

[0111] In some embodiments, the spider silk protein comprises at least two occurrences of a repeat unit, the repeat unit having: more than 150 amino acid residues and a molecular weight of at least 10 kDa; an alanine-rich region having 6 or more consecutive amino acids with an alanine content of at least 80%; a glycine-rich region having 12 or more consecutive amino acids with an alanine content of at least 40% and an alanine content of less than 30%; and the fiber comprises at least one property selected from the group consisting of an elastic modulus of greater than 550 cN / tex, an extensibility of at least 10%, and an ultimate tensile strength of at least 15 cN / tex.

[0112] In some embodiments, the recombinant spider silk protein comprises repeat units, each repeat unit having at least 95% sequence identity to a sequence comprising 2-20 quasi-repeat units; each quasi-repeat unit having a sequence similar to {GGY-[GPG-X1] n1 -GPS-(A) n2}, (SEQ ID NO:3), wherein for each quasi-repeat unit; X1 is SGGQQ (SEQ ID NO:4), GAGQQ (SEQ ID NO:5), GQGPY (SEQ ID NO: 6), AGQQ (SEQ ID NO: 7), and SQ; n1 is 4 to 8, and n2 is 6 to 10. The repeating unit is composed of a plurality of quasi-repeat units.

[0113] In some embodiments, three "long" quasi-repeats are followed by three "short" quasi-repeat units. As noted above, short quasi-repeat units are those where n1=4 or 5. Long quasi-repeat units are defined as those where n1=6, 7 or 8. In some embodiments, all of the short quasi-repeats have the same X1 motif at the same position within each quasi-repeat unit of the repeat unit. In some embodiments, fewer than three quasi-repeat units of the six quasi-repeat units share the same X1 motif.

[0114] In a further embodiment, the repeat unit is made up of quasi-repeat units in which the same X1 does not occur more than two consecutive times within the repeat unit. In a further embodiment, the repeat unit is made up of quasi-repeat units in which at least 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 quasi-repeats do not use the same X1 more than three consecutive times within a single quasi-repeat unit of the repeat unit.

[0115] In some embodiments, the recombinant spider silk polypeptide comprises the polypeptide sequence of SEQ ID NO: 1 (i.e., 18B). In some embodiments, the repeat unit is a polypeptide comprising SEQ ID NO: 2. These sequences are shown in Table 1B. [Table 1B]

[0116] In some embodiments, the structure of the fibers formed from the recombinant spider silk polypeptides described forms a beta-sheet structure, a beta-turn structure, or an alpha-helical structure. In some embodiments, the secondary, tertiary, and quaternary protein structure of the formed fibers is described as having nanocrystalline beta-sheet regions, amorphous beta-turn regions, amorphous alpha-helical regions, randomly spatially distributed nanocrystalline regions embedded in an amorphous matrix, or randomly oriented nanocrystalline regions embedded in an amorphous matrix. Without wishing to be bound by theory, it is believed that the structural properties of the proteins in spider silks are related to the mechanical properties of the fibers. The crystalline regions of the fibers are related to the tensile strength of the fibers, while the amorphous regions are related to the extensibility of the fibers. Major vesicular (MA) silks tend to be stronger and less extensible than flagelliform silks, and similarly, MA silks have a larger volume fraction of crystalline regions compared to flagelliform silks. Furthermore, theoretical models based on the molecular dynamics of crystalline and amorphous regions of spider silk proteins support the assertion that the crystalline regions are related to the tensile strength of the fiber, while the amorphous regions are related to the extensibility of the fiber. Furthermore, theoretical modeling supports the importance of secondary, tertiary, and quaternary structures to the mechanical properties of RPFs. For example, the assembly of nanocrystalline domains in random, parallel, and continuous spatial distributions, as well as the strength of the interaction forces between the entangled chains within the amorphous regions and between the amorphous and nanocrystalline regions, both affect the theoretical mechanical properties of the resulting fibers.

[0117] In some embodiments, the molecular weight of the silk protein is between 20 kDa and 2000 kDa, or greater than 20 kDa, or greater than 10 kDa, or greater than 5 kDa, or between 5 and 400 kDa, or between 5 and 300 kDa, or between 5 and 200 kDa, or between 5 and 100 kDa, or between 5 and 50 kDa, or between 5 and 500 kDa, or between 5 and 1000 kDa, or between 5 and 2000 kDa, or between 10 and 400 kDa, or between 10 and 300 kDa, or between 10 and 200 kDa, or Alternatively, it may be in the range of 10 to 100 kDa, or 10 to 50 kDa, or 10 to 500 kDa, or 10 to 1000 kDa, or 10 to 2000 kDa, or 20 to 400 kDa, or 20 to 300 kDa, or 20 to 200 kDa, or 40 to 300 kDa, or 40 to 500 kDa, or 20 to 100 kDa, or 20 to 50 kDa, or 20 to 500 kDa, or 20 to 1000 kDa, or 20 to 2000 kDa.

[0118] Characterization of impurities and degradation of recombinant spider silk polypeptide powders Different recombinant spider silk polypeptides have different physicochemical properties, such as melting temperature and glass transition temperature, based on the strength and stability of the secondary and tertiary structures that the protein forms. In the form of monomers, silk polypeptides form beta-sheet structures. In the presence of other monomers, silk polypeptides form a three-dimensional crystal lattice of beta-sheet structures. The beta-sheet structures are separate and interspersed with amorphous regions of the polypeptide sequence.

[0119] The beta-sheet structure is very stable at high temperatures, with the melting temperature of beta-sheets being approximately 257°C by fast scanning calorimetry (see Cebe et al., Beating the Heat-Fast Scanning Melts Silk Beta Sheet Crystals, Nature Scientific Reports 3:1130 (2013). Because the beta-sheet structure is believed to remain intact above the glass transition temperature of silk polypeptides, we hypothesize that the structural changes observed at the glass transition temperature of recombinant silk polypeptides are due to increased mobility of the amorphous regions between the beta-sheets.

[0120] Plasticizers can increase the mobility of amorphous regions and hinder the formation of beta-sheets, thus lowering the glass transition temperature and melting temperature of silk proteins. Suitable plasticizers for this purpose include, but are not limited to, water and polyols such as glycerol, triglycerol, hexaglycerol, and decaglycerol. Other suitable plasticizers include, but are not limited to, dimethyl isosorbide; adipic acid; amide of dimethylaminopropylamine with caprylic / capric acid; acetamide, and any combination thereof.

[0121] The hydrophilic portion of silk polypeptide can bind to the surrounding water present in the air as humidity, so that water is almost always present, and the bound surrounding water can plasticize silk polypeptide.In some embodiments, a suitable plasticizer can be glycerol, present alone or in combination with water or other plasticizers.Other suitable plasticizers are as described above.

[0122] In addition, when recombinant spider silk polypeptides are produced by fermentation and recovered as recombinant spider silk polypeptide powder, impurities may be present in the recombinant spider silk polypeptide powder that act as plasticizers or otherwise inhibit the formation of tertiary structures, for example, residual lipids and sugars may act as plasticizers and affect the glass transition temperature of the protein by preventing the formation of tertiary structures.

[0123] A variety of established methods can be used to assess the purity and relative composition of a recombinant spider silk polypeptide powder or composition. Size exclusion chromatography separates molecules based on relative size and can be used to analyze the relative amounts of full-length polymeric and monomeric forms of recombinant spider silk polypeptide, and the amounts of high, low, and medium molecular weight impurities in recombinant spider silk polypeptide powders. Similarly, rapid high performance liquid chromatography can be used to measure the presence of various compounds in solution, such as the monomeric form of recombinant spider silk polypeptide. Ion exchange liquid chromatography can be used to assess the concentration of various trace molecules in solutions containing impurities such as lipids and sugars. Chromatography and other methods for quantification of various molecules, such as mass spectrometry, are well established in the art.

[0124] Depending on the embodiment, the recombinant spider silk polypeptide may have a purity calculated based on the amount of recombinant spider silk polypeptide in monomeric form, using the weight percentages for other components in the recombinant spider silk polypeptide powder. In various cases, the purity may range from 50% to 90% by weight, depending on the type of recombinant spider silk polypeptide and the techniques used to recover, separate and work up the recombinant spider silk polypeptide powder.

[0125] Both size exclusion chromatography and reversed-phase high performance liquid chromatography are useful for measuring full length recombinant spider silk polypeptides, which can be used to determine whether or not the recombinant spider silk polypeptide is degraded during a processing step by comparing the amount of full length spider silk in the polypeptide in the composition before and after processing. In various embodiments of the invention, the amount of full length recombinant spider silk polypeptide in the composition before and after processing may be subject to minimal degradation. The amount of degradation may range from 0.001% to 10% by weight, or 0.01% to 6% by weight, such as 10% by weight, or less than 8% or 6% by weight, or less than 5% by weight, less than 3% by weight, or less than 1% by weight.

[0126] Measurement of glass transition temperature (Tg), secondary and tertiary structure In some embodiments, differential scanning calorimetry is used to determine the glass transition temperature and / or melt transition temperature of the recombinant spider silk polypeptide and / or fibers comprising same, in certain embodiments, modulated differential scanning calorimetry is used to measure the glass transition temperature and / or melt transition temperature.

[0127] Depending on the embodiment and type of recombinant spider silk polypeptide, the glass transition temperature and / or melt transition temperature may have a range of values, however, measurements of glass transition temperature and / or melt transition temperature much lower than normally observed for recombinant spider silk polypeptides in solid form may indicate the presence of impurities or other plasticizers.

[0128] In addition, Fourier transform infrared (FTIR) spectroscopy data can be combined with rheological data to provide direct characterization of the tertiary structure of both recombinant silk powders and / or compositions comprising same. FTIR can be used to quantify the secondary structure of silk polypeptides and / or compositions comprising silk polypeptides, as described below in the section entitled "Fourier transform infrared (FTIR) spectroscopy."

[0129] Depending on the embodiment, FTIR may be used to quantify the amount of beta-sheet structure present in recombinant spider silk polypeptide powders and / or compositions comprising the same. In addition, in some embodiments, FTIR may be used to quantify impurities such as sugars and lipids present in recombinant spider silk polypeptide powders. However, various chaotropic and solubilizing agents used in different protein pretreatment methods may reduce the number of tertiary structures in recombinant spider silk polypeptide powders or compositions comprising the same. Therefore, there may be no correspondence between the amount of beta-sheet structure in recombinant spider silk polypeptide powders before and after they are molded or spun into fibers. Similarly, there may be little correspondence between the glass transition temperature of the powders before and after they are molded or spun into fibers.

[0130] Fourier transform infrared (FTIR) spectra can be used to assess the tertiary structure of proteins present in polypeptide powders and / or fibers. Specifically, FTIR spectra can be used to determine the amount of beta-sheets present in fibers subjected to various spinning and post-treatment conditions. Thus, FTIR spectra can be used to determine the relative amount of beta-sheet structure based on various techniques. Alternatively, FTIR spectra can be compared to natural insect silk.

[0131] Depending on the embodiment, FTIR spectra at different wavenumbers can be used to assess the different tertiary structures present in the fibers. In various embodiments, wavenumbers corresponding to amide I and amide II bands can be used to assess various protein structures such as turns, beta sheets, alpha helices, and side chains. Wavenumbers corresponding to these structures are well known in the art.

[0132] In most embodiments, the amount of beta-sheet structure in the polypeptide powder and / or fiber is assessed using FTIR spectroscopy at wavenumbers corresponding to beta-sheets. In certain embodiments, the amount of beta-sheet structure in the polypeptide powder and / or fiber is evaluated using FTIR spectroscopy at wavenumbers corresponding to beta-sheets. -1 (CH2 Locking (A)n ), 1695~1690cm -1 (Amide I) 1620-1625cm -1 (Amide I), 1440-1445cm -1 (asymmetric CH3 bending) and / or 1508cm -1 FTIR spectra of (amide II) are used to determine the amount of beta-sheets present. Depending on the embodiment, different wavenumbers and ranges can be measured to determine the amount of beta-sheets present. In some embodiments, the 982-949 cm peak can be measured to eliminate interference from the corresponding peaks. -1 FTIR spectra at wavenumbers are used. Exemplary methods for obtaining spectra at these wavenumbers are detailed in Boudet-Audet et al., Identification and classification of silks using infrared spectroscopy, Journal of Experimental Biology, 218:3138-3149 (2015), the entire contents of which are incorporated herein by reference.

[0133] Similarly, various methods for characterization of impurities in recombinant silk powders can be combined with rheological and / or FTIR data to analyze the relationship between the presence of impurities and the formation of secondary and / or tertiary structures.

[0134] Recombinant spider silk molten composition It is an object of the present invention to create a variety of recombinant spider silk compositions that can be converted into a molten or flowable state (i.e., can be converted into a recombinant spider silk molten composition) according to the methods described herein. In various embodiments, the concentrations of recombinant spider silk polypeptide powder and plasticizer in the composition can be varied based on the characteristics of the recombinant spider silk polypeptide powder (e.g., the purity of the recombinant spider silk polypeptide powder), the type of plasticizer used, and the desired properties of the fiber. In some embodiments, the concentrations can be adjusted based on rheological data, such as data from a capillary rheometer.

[0135] Depending on the embodiment, suitable concentrations of recombinant spider silk polypeptide powder in the recombinant spider silk composition range from: 1-25% by weight, 1-30% by weight, up to 70% by weight, 10-60% by weight, 15-50% by weight, 18-45% by weight, or 20-41% by weight.

[0136] In cases where glycerin is used as a plasticizer, suitable weight concentrations of glycerin in the recombinant spider silk composition range from: 1-90% by weight, 10-90% by weight, 10-50% by weight, 10-40% by weight, 15-40% by weight, 10-30% by weight, or 15-30% by weight.

[0137] In cases where water is used as a plasticizer, suitable weight concentrations of water in the recombinant spider silk composition range from: 5-80%, 15-70%, 20-60%, 25-50%, 19-43% or 19-27% by weight. When water is used in combination with another plasticizer, water may be present in the range of 5-50%, 15-43% or 19-27% by weight.

[0138] In some embodiments, water may evaporate during the extrusion and / or cooling process, depending on the process and / or mold size used. In some embodiments, water loss after molding may range from 1-50%, 3-40%, 5-30%, 7-20%, 8-18%, or 10-15% by weight based on the total amount of water. In most cases, the loss is less than 15%, and in some cases, less than 10%, e.g., 1-10% by weight. Evaporation may be either intentional or a result of the process applied. The extent of evaporation may be readily controlled, for example, by selection of the temperature, flow rate, and pressure applied, as understood in the art.

[0139] In some embodiments, suitable plasticizers include polyols (e.g., glycerol), water, lactic acid, ascorbic acid, phosphoric acid, ethylene glycol, propylene glycol, triethanolamine, acid acetate, propane-1,3-diol, or any combination thereof.

[0140] In various embodiments, the amount of plasticizer can vary according to the purity and relative composition of the recombinant spider silk polypeptide powder, for example, a higher purity powder may contain fewer impurities, such as low molecular weight compounds that can act as plasticizers, and therefore require the addition of a larger weight percentage of plasticizer.

[0141] Without wishing to be bound by theory, in various embodiments of the present invention, inducing a recombinant spider silk composition to a flowable state (e.g., inducing a recombinant spider silk molten composition) may be used as a pre-treatment step in any formulation in situations where it is beneficial to include the recombinant spider silk polypeptide in a monomeric form. More specifically, inducing a recombinant spider silk molten composition may be used in applications where it is desirable to prevent the monomeric recombinant spider silk polypeptide from aggregating into a crystalline polymeric form or to control the transition of the recombinant spider silk polypeptide to a crystalline polymeric form at a later stage in the process.

[0142] According to some embodiments of the invention, the recombinant spider silk composition is converted into a molten or flowable state by the application of shear and / or pressure, typically both. Suitable means for achieving a combination of shear and pressure include, but are not limited to, single screw extruders, twin screw extruders, melt flow extruders, and capillary rheometers.

[0143] In some embodiments, a twin screw extruder is used to provide the necessary pressure and shear force to convert the recombinant spider silk composition into a molten or flowable composition. In some embodiments, the twin screw extruder is configured to provide a shear force in the range of 1.5 Newton meters (Nm) to 13 Newton meters, 2 Newton meters to 10 Newton meters, 2 Newton meters to 8 Newton meters, or 2 Newton meters to 6 Newton meters. In some embodiments, the shear force provided by the twin screw extruder is determined in part by the revolutions per minute (RPM) of the twin screw extruder. In various embodiments and configurations, the revolutions per minute (RPM) of the twin screw extruder may range from 10 RPM to 1,000 RPM. In various embodiments, the twin screw extruder is configured to provide a pressure in combination with the shear force in the range of 1 MPa to 300 MPa.

[0144] In any embodiment, the twin screw extruder is configured to heat the recombinant spider silk molten composition before and / or after it is converted into the recombinant spider silk composition. In some embodiments, heat is applied to the barrel of the twin screw extruder (i.e., the cylinder where the twin screws mix the composition). In other embodiments, a portion of the twin screw extruder proximal to the spinneret (i.e., the orifice through which the extruded recombinant spider silk molten composition passes) is heated. Alternatively, no heating is applied and the molten / flowable state is induced entirely by heat resulting from shear forces applied to the recombinant spider silk composition in the twin screw extruder. For example, in some embodiments, the amount of heat applied to achieve the molten / flowable state is equal to ambient room temperature (e.g., greater than about 20° C.).

[0145] In various embodiments, the recombinant spider silk melt composition is heated to a minimum temperature to minimize or completely prevent degradation of the recombinant spider silk polypeptides. In certain embodiments, the recombinant spider silk melt is heated to a temperature below 120° C., below 100° C., below 80° C., below 60° C., below 40° C., or below 20° C. In most cases, the melt will be at a temperature between 10° C. and 120° C., 10° C. and 100° C., 15° C. and 80° C., 15° C. and 60° C., 18° C. and 40° C., or 20±2° C. during processing.

[0146] In other embodiments, other instruments may be used to provide the necessary pressure and shear forces to convert the recombinant spider silk composition into a molten or flowable state. As noted above, a capillary rheometer may be used to provide the necessary shear forces and pressure to convert the recombinant spider silk composition into a flowable or molten state.

[0147] In some embodiments, the recombinant spider silk composition is optionally heated after it is rendered molten or flowable and / or before extruding the molten or flowable recombinant spider silk melt composition. Because heating is likely necessary due to the high glass transition temperature of the recombinant spider silk composition, the device used to provide the shear and pressure to convert the recombinant spider silk composition to a molten or flowable state may be directly or indirectly connected to a heated extrusion device. In certain embodiments, a twin screw cylinder mixer is connected (directly or indirectly) to a heated extrusion device. Depending on the embodiment and configuration of the heated extrusion device, the heated extrusion device may be maintained at a temperature in the range of 20-120°C, 80-110°C, 85-100°C, 85-95°C, and / or 90-95°C.

[0148] The extruded recombinant spider silk molten composition is referred to herein as a "recombinant spider silk extrudate." Depending on the application of the recombinant spider silk extrudate, the diameter of the spinneret through which the extrudate is extruded may be adjusted. For example, in embodiments in which the recombinant spider silk extrudate is extruded into a mold to form a molded body, the spinneret may have a diameter of greater than 200 mm, greater than 150 mm, greater than 100 mm, greater than 50 mm, e.g., in the range of 100 mm to 500 mm, 150 mm to 400 mm, or 200 mm to 300 mm. As described below, in some embodiments, the recombinant spider silk extrudate may be processed into pellets, which may be reprocessed by subjecting the pellets to sufficient shear and pressure to convert the spider silk extrudate into a recombinant spider silk molten composition. In embodiments in which the recombinant spider silk extrudate is processed into pellets, the spinneret may have a diameter greater than 2 mm, greater than 1.5 mm, or greater than 1 mm, for example, in the range of 1 mm to 5 mm, 1.5 mm to 4 mm, or 2 mm to 3 mm.

[0149] In most embodiments of the present invention, both the recombinant spider silk melt composition and the recombinant spider silk extrudate are substantially homogeneous, for example when the resuspended extrudate is examined by optical microscopy or UV / VIS, meaning that the material does not have inclusions or precipitates. In some embodiments, optical microscopy can be used to measure birefringence, which can be interpreted as the alignment of the recombinant spider silk incorporated into a three-dimensional lattice. Birefringence is an optical property of a material that has a refractive index that depends on the polarization and propagation of light. Specifically, a high degree of axial order, as measured by birefringence, can be associated with high tensile strength. In some embodiments, the recombinant spider silk melt extrudate has minimal birefringence.

[0150] According to the present invention, the homogeneous flowable state can be induced only by the application of shear and pressure, optionally with heat. It has been found that the combination of shear and pressure alone, without the application of heat or with the optional application of heat, provides a recombinant spider silk molten composition and a composition that does not degrade during the processing of the recombinant spider silk polypeptide in the recombinant spider silk extrudate. This is desirable and beneficial, as the retention of full-length recombinant spider silk polypeptide in the extruded composition achieves optimal material properties, such as crystallinity, resulting in a higher quality product. In an embodiment of the present invention, the recombinant spider silk molten extrudate achieved using shear and pressure (and optionally heat) shows minimal or negligible degradation.

[0151] The amount of degradation of the recombinant spider silk polypeptide can be measured using various techniques. As described above, the amount of degradation of the recombinant spider silk polypeptide can be measured using size exclusion chromatography to measure the amount of full-length recombinant spider silk polypeptide present. In various embodiments, after forming the composition into a molded body, less than 6.0% by weight of the composition degrades. In other embodiments, after forming the composition, less than 4.0%, less than 3.0%, less than 2.0%, or less than 1.0% by weight of the composition degrades (such that the amount of degradation is within the range of 0.001% to 10%, 8%, 6%, 4%, 3%, 2%, or 1%, or 0.01% to 6%, 4%, 3%, 2%, or 1% by weight). In other embodiments, the recombinant spider silk protein in the extrudate and / or molten composition is not substantially degraded.

[0152] Incorporating the extrudate into a cosmetic formulation In various embodiments, the recombinant spider silk extrudates are incorporated into spider silk cosmetic or skin care products (e.g., solutions to be applied to skin or hair). Specifically, the recombinant spider silk extrudates may be used as a base for cosmetic or skin care products, and the recombinant spider silk polypeptide is present in its monomeric or low crystalline form. Without wishing to be bound by theory, the application of shear and pressure to the recombinant spider silk polypeptide in the presence of a plasticizer such as glycerol transforms the recombinant spider silk polypeptide into an "open recombinant spider silk polypeptide" in which the recombinant spider silk polypeptide is unfolded and exhibits interactions with glycerol. Due to the interaction with glycerol, this "open recombinant spider silk polypeptide" exhibits reduced intermolecular and intramolecular beta-sheet interactions. Specifically, the open recombinant spider silk polypeptide forms intermolecular interactions that prevent the formation of an irreversible three-dimensional lattice.

[0153] Without intending to be limited by theory, the incorporation of recombinant spider silk polypeptides in an open state into skin care formulations can control the aggregation of the recombinant spider silk polypeptide into a crystalline polymeric form upon contact with the skin or through various other chemical reactions. Similarly, maintaining the recombinant spider silk polypeptide in an open state in a low crystalline form can increase the stability of the recombinant spider silk polypeptide in cosmetic formulations or skin care products by preventing self-aggregation of the recombinant spider silk polypeptide. As described below, in various embodiments, the recombinant spider silk extrudates can form dispersible semi-solid or gel-like structures at relatively low melting temperatures (Tm). In various embodiments of incorporating recombinant spider silk extrudates into skin care formulations, the recombinant spider silk extrudates can form reversible three-dimensional structures, such as gels or films that melt into dispersible liquids on the surface of the skin.

[0154] In various embodiments, the recombinant spider silk extrudates may be suspended in water ("aqueous suspension extrudates") to form a gel or base that can be incorporated (i.e., formulated) into cosmetic or skin care formulations. Depending on the embodiment, the amount of recombinant spider silk extrudate to water in the aqueous suspension extrudate can vary, as can the relative ratio of recombinant spider silk polypeptide powder to glycerol in the recombinant spider silk extrudate. In some embodiments, the extrudate composition comprises 10-33% by weight recombinant silk polypeptide powder and 67-90% by weight glycerol. In some embodiments, a plasticizer different from glycerol is used. In some embodiments, the recombinant spider silk extrudates are suspended in water to create an aqueous suspension extrudate that is 1-40% recombinant spider silk extrudate and 60-99% water. In certain embodiments, the extrudate composition is suspended in water to create an aqueous suspension extrudate that is 10% by weight recombinant silk polypeptide powder, 30% by weight glycerol, and 60% by weight water. In certain embodiments, the extrudate is suspended in water to create an aqueous suspension extrudate that is 6% by weight recombinant silk polypeptide powder, 18% by weight glycerol, and 76% by weight water.

[0155] Depending on the embodiment, the aqueous suspension extrudate may be optionally heated and stirred once it is resuspended in water. In some embodiments, heating and stirring the aqueous suspension extrudate may result in a phase change of the recombinant spider silk polypeptide in the aqueous suspension extrudate. Specifically, heating and stirring the aqueous suspension precipitate results in three distinct phases that are assessed by centrifugation: 1) a gel phase that is distinct from the supernatant after centrifugation; 2) a colloidal phase that can be filtered from the supernatant after centrifugation; and 3) a solution phase that remains after filtering the colloidal phase from the supernatant. Various combinations of heat, stirring, and centrifugation may be used to prevent degradation of the recombinant spider silk polypeptide, provided that the aqueous suspension extrudate is not exposed to heat for extended periods of time. In certain embodiments, the extrudate is gently stirred at 90° C. for 5 minutes and centrifuged at 16,000 RCF for 30 minutes.

[0156] In some embodiments, any of the various phases of the aqueous suspension extrudate (i.e., colloidal phase, gel phase, and solution) or the aqueous suspension extrudate may be incorporated into a cosmetic or skin care formulation to provide a source of recombinant spider silk protein in an open state. Depending on the embodiment, the aqueous suspension extrudate may be agitated with or without heat prior to incorporation into the skin care formulation. Optionally, the aqueous suspension extrudate may be separated at the steps described above by centrifugation and / or filtration. Depending on the embodiment, the skin care formulation may be an emulsion (e.g., a cream or serum) or an aqueous-based solution (e.g., a gel). In certain embodiments, the recombinant spider silk extrudate may be incorporated into any of the cosmetic or skin care formulations described above without resuspension in water. In these compositions, a homogenizer or similar device may be used to ensure that the recombinant spider silk extrudate is uniformly distributed in the composition.

[0157] In some embodiments, the colloidal phase (i.e., colloidal suspension) comprises particles of various sizes comprising recombinant spider silk protein. In some embodiments, the particle sizes range from 1 nm to 10,000 nm, 10 nm to 5,000 nm, or 20 nm to 3000 nm in diameter. In some embodiments, the majority of the particles in the colloidal suspension range from 50 nm to 2,000 nm. In some embodiments, the colloidal suspension has an average particle diameter of about 350 nm. In some embodiments, the average particle diameter is 300 nm to 400 nm, 200 nm to 500 nm, or 100 nm to 1,000 nm. In some embodiments, the colloidal suspension has a polydispersity index of about 0.5 as measured by a Malvern Zetasizer Nano instrument. In some embodiments, the polydispersity index is 0.4 to 0.6, 0.3 to 0.7, 0.2 to 0.8, or 0.1 to 1.0. In some embodiments, the polydispersity index is greater than 0.05, greater than 0.1, greater than 0.2, greater than 0.3, or greater than 0.4. In some embodiments, the distribution of particles in the colloidal suspension comprises two or more peaks.

[0158] In some embodiments, the aqueous suspension extrudate may be heated and stirred, then cast onto a flat surface, and dried into a film. In some embodiments, the aqueous suspension extrudate may be incorporated into an emulsion, then cast onto a flat surface, and dried into a film. Depending on the embodiment, a variety of different drying conditions may be used. Suitable drying conditions include drying at 60° C. with or without a vacuum. In embodiments using a vacuum, 15 Hg is a suitable amount of vacuum. Other drying methods are well established in the art.

[0159] In various embodiments, the melting temperature of the film containing only the aqueous suspension extrudate in the emulsion is low. In various embodiments, the melting temperature of the film containing only the aqueous suspension extrudate in the emulsion is lower than body temperature (about 34-36°C) and melts on contact with the skin. Without intending to be limited by theory, the recombinant spider silk polypeptide in the open state exhibits sufficient intermolecular interactions to create a semi-solid structure (i.e., a film), which can act reversibly upon skin contact to reform after dispersion on the skin surface. As described below, when a slurry of recombinant silk polypeptide powder and glycerol is suspended in an aqueous solution, it does not form a film upon drying, but forms the same slurry as before suspension. In various embodiments, the film has reduced crystallinity as measured by FTIR compared to the recombinant spider silk polypeptide powder or recombinant spider silk extrudate.

[0160] In another specific embodiment, the aqueous suspension extrudate or extrudate can be placed into an emulsion (e.g., homogenized) and then cast onto a flat surface and freeze-dried to create a porous film. Depending on the embodiment, various techniques can be used for freeze-drying, such as freezing the film at -80°C for 30 minutes. Other freeze-drying techniques are known to those skilled in the art. In various embodiments, the melting temperature of a freeze-dried porous film containing an emulsion containing only an aqueous suspension extrudate is lower than body temperature (about 34-36°C) and melts on contact with the skin.

[0161] In various embodiments, the above-mentioned film can be used as a topical skin care agent. The film can be applied directly to the skin and can form a dispersible viscous material that is absorbed into the skin when rehydrated. As discussed below, various emollients, moisturizers, actives, and other cosmetic adjuvants can be incorporated into the film. The film can be applied directly to the skin and can be absorbed by contact with the skin or when the facial pack is gently rubbed against the skin. In some embodiments, the extrudate resuspended in an aqueous solution can be applied to the face and then exposed to a coagulating agent such as propylene glycol via mist to form a gellable facial pack.

[0162] Depending on the embodiment, the cast film may be a flat (i.e., unaltered surface) film that can be cast into a mold incorporating microstructures, in certain embodiments, the film is cast into a mold incorporating microneedle structures that pierce the surface of the skin and aid in the delivery of active agents.

[0163] In an alternative embodiment, the aqueous suspension extrudate may be added to an emulsion for use as a skin care product. The emulsion may be applied to the skin and then upon drying, form a film on the surface of the skin. As discussed below, various emollients, moisturizers, actives, and other cosmetic adjuvants may be incorporated into the emulsion.

[0164] Compositions including emulsions and films The emulsions and films described above may contain a variety of moisturizers, emollients, occlusive agents, active agents, and cosmetic adjuvants depending on the embodiment and the desired benefits of the formulation.

[0165] The term "humectant" as used herein refers to a hygroscopic substance that forms bonds with water molecules.Suitable humectants include, but are not limited to, glycerol, propylene glycol, polyethylene glycol, pentylene glycol, tremella extract, sorbitol, dicyanamide, sodium lactate, hyaluronic acid, aloe vera extract, alpha-hydroxy acid, and pyrrolidone carboxylate (NaPCA).The term "emollient" as used herein refers to a compound that fills the gaps on the skin surface and gives the skin a soft or smooth appearance. Suitable emollients include, but are not limited to, shea butter, cocoa butter, squalene, squalane, octyl octanoate, sesame oil, grape seed oil, natural oils containing oleic acid (e.g., sweet almond oil, argan oil, olive oil, avocado oil), natural oils containing gamma linoleic acid (e.g., evening primrose oil, borage oil), natural oils containing linoleic acid (e.g., safflower oil, sunflower oil), or any combination thereof. The term "occlusive agent" refers to a compound that forms a barrier on the skin surface to retain moisture. In some cases, an emollient or moisturizer may be an occlusive agent. Other suitable occlusive agents include, but are not limited to, beeswax, carnauba wax, ceramides, vegetable waxes, lecithin, and allantoin. Without being limited by theory, the film-forming ability of the recombinant spider silk compositions presented herein creates an occlusive agent that attracts water molecules and also acts as a moisturizer, thus forming a moisturizing barrier.

[0166] In some embodiments, the emulsions and films described herein form a barrier on the skin surface that prevents or reduces transepidermal water loss from damaged skin. In some embodiments, the transepidermal water loss measured by moisture evaporometer is less than 10 after application of the barrier to the skin surface. In some embodiments, the transepidermal water loss is reduced by more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 55%, more than 60%, more than 65%, more than 70%, or more than 75% compared to damaged untreated skin.

[0167] The term "active agent" refers to any compound that exhibits known efficacy in skin care formulations or sunscreens. Various active agents include, but are not limited to, acetic acid (i.e., vitamin C), alpha hydroxyl acids, beta hydroxyl acids, zinc oxide, titanium dioxide, retinol, niacinamide, other recombinant proteins (either full-length sequences or hydrolyzed to subsequences or "peptides"), copper peptides, curcuminoids, glycolic acid, hydroquinone, kojic acid, l-ascorbic acid, alpha lipoic acid, azelaic acid, lactic acid, ferulic acid, mandelic acid, dimethylaminoethanol (DMAE), resveratrol, natural extracts containing antioxidants (e.g., green tea extract, pine tree extract), caffeine, alpha arbutin, coenzyme Q-10, and salicylic acid. The term "cosmetic adjuvants" refers to various other agents used to produce cosmetic products with commercially desirable properties, including, but not limited to, surfactants, emulsifiers, preservatives, and thickeners.

[0168] Coagulant In some embodiments, the silk-based composition produced herein is exposed to a coagulating agent, which alters the properties of the composition and facilitates the control of silk aggregation in the silk-based composition. In some embodiments, the silk-based composition is immersed in the coagulating agent. In some embodiments, the silk-based composition is exposed to a mist or vapor of the coagulating agent. In some embodiments, the aqueous extrudate composition includes, is immersed in, or is mixed with the coagulating agent. In some embodiments, a silk-based solid or semi-solid, such as a film, is immersed in, or is exposed to a vapor containing the coagulating agent. In some embodiments, methanol is used as an effective coagulating agent.

[0169] In some embodiments, alcohol, such as isopropanol, ethanol, or methanol, can be used as the coagulant. In some embodiments, 60%, 70%, 80%, 90%, or 100% alcohol is used as the coagulant. In some embodiments, salt, such as ammonium sulfate, sodium chloride, sodium sulfate, or other protein precipitating salts that are effective at temperatures between 20-60° C., can be used as the coagulant.

[0170] In some embodiments, a combination of one or more of water, acids, solvents, and salts can be used as the coagulant, including but not limited to the following classes of chemicals: Bronsted-Lowry acids, Lewis acids, binary hydride acids, organic acids, metal cation acids, organic solvents, inorganic solvents, alkali metal salts, and alkaline earth metal salts. In some embodiments, the acid includes dilute hydrochloric acid, dilute sulfuric acid, formic acid, or acetic acid. In some embodiments, the solvent includes ethanol, methanol, isopropanol, t-butyl alcohol, ethyl acetate, propylene glycol, or ethylene glycol. In some embodiments, the salt includes LiCl, KCl, BeCl2, MgCl2, CaCl2, NaCl, ZnCl2, FeCl3, ammonium sulfate, sodium sulfate, sodium acetate, and other salts, such as nitrates, sulfates, or phosphates. In some embodiments, the pH of the coagulant is between 2.5 and 7.5. EXAMPLES

[0171] Example 1: Purity of Recombinant 18B Polypeptide Powder Recombinant spider silk - 18B polypeptide sequence (SEQ ID NO: 1) containing a FLAG tag - was produced in various lots of large-scale fermentations, harvested as a powder ("18B powder"), and dried. Reverse-phase high-performance liquid chromatography ("RP-HPLC") was used to measure the weight amount of 18B polypeptide monomer in the powder. 5M guanidine thiocyanate (GdSCN) reagent was used to dissolve the samples and injected into an Agilent Poroshell 300SB C3 2.1x75mm 5μm column to separate the components based on hydrophobicity. The detection method was UV absorbance of the peptide bond at 215nm (360nm reference). Sample concentrations of 18B-FLAG monomer were determined by comparison to 18B-FLAG powder standards, which had previously determined 18B-FLAG monomer concentrations, using size-exclusion chromatography (SEC-HPLC).

[0172] The sample powder contained 57.964% by weight of 18B monomer.

[0173] Example 2: Silk powder extrudate mixture Silk extrudate mixtures were formed as follows: The recombinant silk powder from Example 1 was mixed using a household spice grinder. Water and glycerol were added to the recombinant silk powder ("18B powder") in the ratios shown in Table 2 below to produce recombinant spider silk compositions with different ratios of protein powder and plasticizer.

[0174] Batches of 10-100 grams of recombinant spider silk composition (i.e., "formulation") as described in Table 2 below were mixed using an Xceptional Instruments Twin Screw Extruder (TSE) (item number TT-ZE5-MSMS-3HT) that was used for all TSE experiments. The stainless steel (S316) extruder barrel had three heating zones, each approximately 5 cm in length. The screws used were standard twin stainless steel (S316) co-rotating screws, 180 mm long, 9 mm in diameter, and (20:1 L / D ratio). The screw pitch was 9 mm.

[0175] For the P49W21G30 and P65W20G15 formulations described below, the recombinant spider silk composition was first extruded into pellets, which were then re-extruded and reprocessed in subsequent experiments. To create pellets, the recombinant spider silk composition, including the 18B / water / glycerol mixture, was introduced into the TSE using a metal funnel and forced into the twin screw using a loading device while the TSE was running at 300 RPM and at a temperature of about 90-95° C. for all three barrel sections, including the beginning, middle, and end barrel sections, for several minutes in continuous contact. The material was extruded in the molten state (i.e., the recombinant spider silk molten composition) through a 0.5 mm die with an orifice at an angle of 180° to the screw axis to form the recombinant spider silk extrudate.

[0176] The 0.5 mm recombinant spider silk extrudates emerged from the mold as continuous elastomeric "noodles" approximately 10 meters in length. 5-10 g amounts of the corresponding extrudate compositions were sequentially placed into a kitchen spice grinder and pulsed for 5 seconds for a total of six pulses (30 seconds total) to produce pellets. The pellets were inspected to confirm that the pellets were 5 mm or less in length, with the average pellet length being approximately 2.5 mm.

[0177] For the following P71W19G10 formulations, the 18B / water / glycerol recombinant spider silk mixture was pre-mixed under the conditions described in Example 2 and directly extruded (i.e., without first being extruded as pellets) to form recombinant spider silk extrudates. [Table 2]

[0178] Example 3: Production of recombinant silk extrudates with minimal degradation - P49W21G30 To assess degradation under several different conditions, the recombinant spider silk formulations described in Example 2 were subjected to different temperatures as well as different pressures and shear forces during extrusion. Specifically, the revolutions per minute of the twin-screw extruder pellets were varied to apply variable amounts of torque and shear forces. The different temperature and RPM combinations used to convert the recombinant spider silk formulations to a molten state and extrude the various samples are listed below.

[0179] Pellets obtained by extruding the P49W21G30 and P65W20G15 formulations described in Table 1 were extruded at various RPMs and temperatures using an Xceptional Instruments TSE. Other parameters for the operation of the Xceptional Instruments TSE were the same as those described for Example 2.

[0180] The P71W19G10 formulation was also extruded at various RPMs and temperatures using an Xceptional Instruments TSE as described in Example 2. Other parameters for the operation of the Xceptional Instruments TSE were the same as those described for Example 2.

[0181] Size exclusion chromatography (SEC) was used to collect data characterizing the relative amounts of high, low, and medium molecular weight impurities, monomeric 18B, and aggregated 18B as follows: 18B powder was dissolved in 5 M guanidine thiocyanate and injected onto a Yarra SEC-3000 SEC-HPLC column to separate components based on molecular weight. Refractive index was used as the detection method. 18B aggregates, 18B monomer, low molecular weight (1-8 kDa), medium molecular weight (8-50 kDa), and high molecular weight (110-150 kDa) impurities were quantified. Relevant compositions were reported as mass % and area %. BSA was used as a common protein standard under the assumption that >90% of all proteins exhibit dn / dc values ​​(refractive index response factor) within about 7% of each other. Poly(ethylene oxide) was used as the retention time standard, and BSA calibrators were used as check standards to ensure consistent performance of the method.

[0182] Tables 3-5 below show various SEC analyses of extrudates produced at various RPMs and temperatures. The fifth column lists either the difference in 18B monomer (area %) reported for the starting pellets and extrudates (P49W21G30 and P65W20G15) or the difference in 18B monomer (area %) reported for the starting powder and extrudate (P71W19G10). Figures 1-3 are detailed below and include graphs corresponding to Tables 3-5, respectively. From these, it can be seen that there was minimal decomposition at all temperatures and RPMs tested, indicating flexibility in processing conditions and general reliability for processing using the extrusion method. [Table 3] [Table 4] [Table 5]

[0183] Figure 1 shows the SEC data for the P49W21G30 samples listed in Table 3 above under extrusion conditions of 20, 40, 60, 80, 95, or 120°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, or 300 RPM. The 18B monomer (black bars), mid molecular weight impurities (gray bars), and low molecular weight impurities (cross-hatched bars) are shown as area %.

[0184] Figure 2 shows the SEC data for the P65W20G15 samples listed in Table 4 above under extrusion conditions of 20, 40, 60, 95, or 140°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, or 300 RPM. The 18B monomer (black bars), mid molecular weight impurities (gray bars), and low molecular weight impurities (cross-hatched bars) are shown as area %.

[0185] Figure 3 shows the SEC data for the P71W19G10 samples listed in Table 5 above under extrusion conditions of 90 or 120°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, or 300 RPM. The 18B monomer (black bars), mid molecular weight impurities (gray bars), and low molecular weight impurities (cross-hatched bars) are shown as area %.

[0186] Example 4: Thermogravimetric Analysis - P49W21G30 To analyze the moisture loss during extrusion, the moisture of the recombinant spider silk composition before extrusion and the recombinant spider silk extrudate after extrusion was analyzed by TGA (thermogravimetric analysis) using a TA brand TGAQ 500 instrument. For the P49W21G30 and P65W20G15 samples, the moisture of the pellets used in the extrusion experiments described in Example 3 was used as a reference sample to measure the moisture loss. For the P71W19G10 sample, the moisture of the recombinant spider silk composition used in the extrusion experiments described in Example 3 was used as a reference sample to measure the moisture loss.

[0187] For each sample, 10 mg, + / - 1 mg of powder or pellets containing the above formulation were analyzed. To measure moisture content, samples were used in "air" rather than "nitrogen". The equipped autosampler was used to sequentially introduce the samples into the TGA oven. Using the TA brand software suite, the temperature was programmed to increase from room temperature at a rate of 20°C / min until it reached 110°C. The samples were then held at this temperature for 45 minutes. The samples were then removed from the oven and the oven was purged with air for 15 minutes before the next run was started.

[0188] Tables 6-8 below show various measurements for the reference samples (i.e., starting pellets or powder) and the extruded samples. Figures 4-6 depict graphs of the data contained in Tables 6-8, respectively. From these data, it can be seen that the water loss during extrusion is low and well within the tolerances of the extrusion process. Typically, the water loss is in the range of 2-18%. [Table 6] [Table 7] [Table 8]

[0189] Figure 4 shows the TGA data for the samples described in Table 6 above produced under extrusion conditions of 20, 40, 95, and 120°C, with the extrudates obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Figure 4 also shows the TGA data for a reference sample of the starting pellets used to produce these samples. The data shows the moisture content of the samples for all treatments, with moisture loss ranging from about 1-13% when compared to the starting pellets.

[0190] Figure 5 shows TGA data for the samples described in Table 7 above produced under extrusion conditions of 20, 40, 60, and 140°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Figure 5 also shows TGA data for a reference sample of the starting pellets used to produce these samples. This data shows the moisture content of the samples for all treatments, with moisture loss ranging from about 1-8% when compared to the starting pellets.

[0191] Figure 6 shows the TGA data for the samples described in Table 8 above produced under extrusion conditions of 90 and 120°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Figure 5 also shows the TGA data for a reference sample of the starting powder used to produce these samples. This data shows the moisture content of the samples for all treatments, with moisture loss ranging from about 1.5 to 4% when compared to the starting powder.

[0192] Example 5: Beta-sheet content analysis using Fourier transform infrared spectroscopy To assess the formation of secondary and tertiary structures in the extrudates, the beta-sheet content was measured by FTIR (Fourier transform infrared spectroscopy). FTIR was performed on the extrudates using a Bruker Alpha spectrometer equipped with a diamond attenuated total reflection accessory in front of a wire grid polarizer, selecting primarily S (vertical) polarized light. Recombinant polypeptide powder and precursor fibers were used as controls. To quantify the molecular alignment, three spectra of each orientation (0 and 90° to the polarizing field) were obtained using a 4 cm -1 Resolution of 4000-600 cm -1 were collected in 32 scans.

[0193] 982~949cm -1 The average value of the peaks corresponding to the bands was calculated based on the following procedure. -1Next, the average of the 1350–1315 cm bands corresponding to the isotropic (non-oriented) side chain vibration band was subtracted. -1 The spectra were normalized by dividing the average of the β-sheet content by the mean of the 982–949 cm -1 The absorbance was taken as the average of the integrated absorbance values.

[0194] The beta-sheet content of the recombinant spider silk extrudates (i.e., "sample beta-sheet") was compared to i) the beta-sheet content of the starting recombinant spider silk polypeptide powder used to generate the recombinant spider silk composition (i.e., "reference pre-hydrated powder"), and ii) the beta-sheet content of the starting pellets (P49W21G30 and P65W20G15) (i.e., "reference pellets"). Tables 9-11 below list the measurements of the reference samples and extrudates generated under the conditions shown in the tables. Figures 7-9 provide graphs of the data shown in Tables 9-11. As shown therein, there was no significant change in the beta-sheet content of the material from the initial recombinant silk polypeptide powder to the recombinant spider silk extrudates, indicating that this method allows for the plasticization and movement of amorphous protein domains without disrupting the beta-sheets, as occurs when solvent treatments are used. [Table 9] [Table 10] [Table 11]

[0195] Figure 7 shows FTIR data for samples from Table 9 above produced under extrusion conditions of 20, 40, 60, 80, 95, or 120°C, with the extrudates obtained at each temperature using operating parameters of 10, 100, 200, or 300 RPM. Data was extracted from the 949-982 band and no clear trends were observed compared to the starting pellets.

[0196] Figure 8 shows FTIR data for samples from Table 10 above produced under extrusion conditions of 20, 40, 60, 95, or 140°C, with the extrudates obtained at each temperature using operating parameters of 10, 100, 200, or 300 RPM. Data was extracted from the 949-982 band and no clear trends were observed compared to the starting pellets.

[0197] Figure 9 shows FTIR data for the samples listed in Table 11 above produced under extrusion conditions of 90 or 120°C, with the extrudates obtained at each temperature using operating parameters of 10, 100, 200 or 300 RPM. The data was taken from the 949-982 band to avoid effects due to the presence of water, and no clear trends were observed compared to the starting pellets.

[0198] Example 6: Polarizing Microscope - P49W21G30 Polarized light microscopy (PL) was used to examine the smoothness and uniformity of the various extrudates. Optical and polarized light (PL) images were obtained using a Leica DM750P polarized light microscope equipped with a 4X PL objective. This microscope was connected to a complementary PC-based image analysis Leica Application Suite, LAS V4.9. TSE extrudates of approximately 20-30 mm in length were carefully positioned along the long axis of a standard microscope slide and placed horizontally (East-West; i.e., 0°) in the aperture of the microscope. The edge of the sample was first focused, and then the entire sample was brought into focus. First, the samples were observed under white light, controlled by the illumination control knob, and images were captured with the appropriate scale bar included. In all cases, the auto-brightness function of the LAS V4.9 software was switched off.

[0199] The Analyzer / Bertrand Lens module was then fitted by flipping its lower rocker to the right ("A" position / Analyzer in) while ensuring that its upper rocker was flipped to the left ("O" position / Bertrand Lens out). Such a setup allows for analysis in "cross-polarized mode" with optical alignment such that the allowed vibration directions of light passing through the polarizer and analyzer are 90°.

[0200] To control for background variations in light intensity, all samples were first displayed and the illumination control knob was turned down until the background brightness was completely black. Each eyepiece was then covered with an eyepiece light shielding accessory to prevent the passage of ambient light into the image capture sequence. Images were captured at 0° and 45° orientations using the LAS V4.9 software package. The microscope's circular rotating stage was used to rotate the glass side to a 45° angle to obtain 45° images.

[0201] Figures 10 and 11 are images of exemplary samples captured using polarized light microscopy. They show that smooth fibers with little melt fracture are obtained using the claimed process. Thus, the conditions are clearly favorable for melt flow and extrusion. In addition, qualitative birefringence as well as axial alignment were observed under a number of conditions.

[0202] Figure 10 shows the photographs taken for samples P49W21G30-1, P49W21G30-2, P49W21G30-3, and P49W21G30-4, all of which were produced at various RPMs at 20°C. Under these conditions, the extrudates were smooth with minimal melt fracture. Polarized light microscopy showed preferential axial alignment depending on the conditions (examine at 45° for differences), with the best axial alignment being obtained at 100 RPM.

[0203] FIG. 11 shows the photographs obtained for samples P49W21G30-17, P49W21G30-18, P49W21G30-19, and P49W21G30-20, all produced at various RPMs at 95°C. The extrudates showed moderate melt fracture / surface imperfections. Polarized light microscopy showed good axial alignment from 10 to 100 RPM. The 100 to 300 RPM samples showed similar characteristics to each other when examined at 0° and 45°.

[0204] Example 7: Metabolite analysis of glycerol content To determine the loss of glycerol in the recombinant spider silk compositions during extrusion, the glycerol content was analyzed using a Benson Polymeric 150x7.8mm H+ 7110-0 HPLC column equipped with a Phenomenex Security Guard Carbo H+ Guard Column using a mobile phase of 0.004M sulfuric acid. To allow for quantification, glycerol calibrators were first analyzed. To measure the amount of glycerol in the 18B-based samples, the glycerol content in the compositions was measured before extrusion (i.e., as pellets or powder) and after extrusion. For each sample, 25 mg of powder or pellets were dissolved in 1 ml of 0.004M sulfuric acid and sonicated for 1 hour. The samples were then vortexed and placed in HPLC vials for subsequent analysis at each condition / treatment.

[0205] Tables 12-14 below show various measurements of extrudates produced under the conditions in the following tables. Figures 12-14 show graphs of the same samples. From these, it can be seen that the glycerol content of the composition is stable over the range of conditions tested, as evidenced by minimal loss in the tests. [Table 12] [Table 13] [Table 14]

[0206] Figure 12 shows metabolite data for samples from Table 12 above produced under extrusion conditions of 20, 40, 60, 80, 95, and 120°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Glycerol loss was negligible in all treatments.

[0207] Figure 13 shows metabolite data for samples from Table 13 above produced under extrusion conditions of 20, 40, 60, 95, and 140°C, with extrudates obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Glycerol loss was negligible in all treatments.

[0208] Figure 14 shows metabolite data for samples produced under extrusion conditions of 90 and 120°C, as described in Table 14 above, where extrudates were obtained at each temperature using operating parameters of 10, 100, 200, and 300 RPM. Glycerol loss was negligible in all treatments.

[0209] Example 8: Microscopic analysis of silk-glycerol extrudates To investigate the effect of circulation duration on the morphology of recombinant spider silk in extrudates subjected to shear and pressure, recombinant spider silk polypeptide powder similar to that described in Example 1 was mixed with glycerin and subjected to different circulation durations for various times at a temperature of 90°C in an Xplore MC 15 conical twin screw extruder (Xplore TSE).

[0210] Volume weight formulations of 10% silk and 90% glycerol ("10% silk"); 17% silk and 83% glycerol ("17% silk"), and 25% silk and 75% glycerol ("25% silk") were circulated in the XPlore TSE at 90°C for 0.5, 0.5, and 2 hours, respectively, and then extruded from the XPlore TSE. The resulting extrudates were examined using a Leica 2700M optical microscope for recombinant spider silk morphology and a set of visual criteria for dissolved recombinant spider silk, undissolved recombinant spider silk, and recombinant spider silk powder. Figure 15 shows the extrudates obtained from the mixtures and methods described above, as well as the undissolved powder reference (i.e., a mixture of glycerol and silk powder prior to extrusion). As shown in FIG. 15, the 10% silk extrudate appeared to be undissolved when compared to a morphological reference, while the 17% silk extrudate and the 25% silk extrudate appeared to be dissolved when compared to a morphological reference developed using known standards for undissolved powder.

[0211] A 25% silk formulation was also circulated in an XPlore TSE at 90° C. for 30 seconds, 4 minutes, 5 minutes, 10 minutes, 20 minutes, 0.5 hours, 1 hour, and 1.5 hours, and then extruded. The extrudates obtained after various circulations were examined for morphological changes due to the length of circulation time using a Leica 2700M optical microscope. Images of the optical microscopy performed on each extrudate are shown in FIG. 16. No morphological differences due to prolonged circulation were observed when examined by optical microscopy.

[0212] Using another recombinant spider silk protein powder lot similar in composition to Example 1, various 25% silk formulations were analyzed for proteolysis after extrusion as outlined in the methods above for Example 3. The results are shown below in Table 15. As shown in Table 15, cycling at 90° C. resulted in minimal degradation, but increased degradation occurred with increasing cycling time. [Table 15]

[0213] The solubility of spider silk protein extrudates was evaluated as a function of circulation time during extrusion. Specifically, a mixture of 25% recombinant spider silk polypeptide powder and 75% glycerol was circulated in the twin-screw extruder described above for times of 30 seconds, 4 minutes, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 60 minutes, and 90 minutes. Each resulting extrudate was resuspended in a mixture of 80% water and 20% extrudate and examined using an optical microscope. As shown in Figure 16, the solubility increased over time, but did not increase further beyond 30 minutes.

[0214] Example 9: Phase separation of recombinant spider silk extrudates To characterize the recombinant spider silk extrudates in aqueous solutions, 25% recombinant spider silk powder and 75% glycerol extrudates described in Example 8, circulated at 250 RPM for 30 minutes, were gently suspended in various amounts of deionized water and stirred in room temperature (21° C.) water to disintegrate. In some cases, the extrudate and water suspension was then heated at 90° C. for 10 minutes while stirring the water containing the extrudate. FIG. 17 shows the morphology analysis of the extrudates, extrudates resuspended in water, and extrudates after stirring at room temperature or 90° C. obtained using optical microscopy as described in Example 8. Specifically, a volumetric suspension of 60% water and 40% silk extrudates produced a suspension containing 10% recombinant silk protein powder, 30% glycerol, and 60% water. The suspension was gently stirred at room temperature for 30 minutes or at 90° C. for 10 minutes. A suspension of 76% water and 24% silk extrudate by volume yielded a suspension containing 6% recombinant spider silk protein powder, 18% glycerin, and 76% water, which was stirred at 90° C. for 10 minutes.

[0215] After heating, the aqueous extrudate suspension containing 6% spider silk protein powder, 18% glycerin, and 76% water was centrifuged to induce phase separation towards three distinct phases: gel phase, colloid phase, and solution phase. First, as shown in FIG. 18, the extrudate and water suspension was centrifuged at 16,000 RCF at room temperature for 30 minutes, a viscous gel phase appeared and formed a pellet at the bottom of the tube, and then a colloidal supernatant phase (including the solution phase and the colloidal phase) appeared and formed an opaque supernatant that did not settle over time. The colloidal supernatant phase was centrifuged at 16,000 RCF at 4° C. for 30 minutes to obtain the solution phase, and a clear supernatant appeared. The aqueous extrudate suspension, gel phase, colloidal supernatant phase, and solution phase were each imaged using an optical microscope. Dried films were formed from each of these phases. Actual photographs of each phase, optical micrographs, and images of the dried films produced from each phase are shown in FIG.

[0216] Example 10: Film Formation To investigate the film-forming properties of the recombinant spider silk extrudates, aqueous suspension extrudates were used to produce a variety of films.

[0217] A "silk-glycerol film" was formed using recombinant spider silk extrudates produced using the process described in Example 8. Specifically, a mixture of 25% by weight recombinant spider silk polypeptide powder and 75% by weight glycerol was circulated in a twin screw extruder at 90°C and 250 RPM for 30 minutes to produce recombinant spider silk extrudates. A suspension of 20% by weight recombinant spider silk extrudates and 80% by weight deionized water was then produced to obtain an aqueous suspension extrudate. The extrudate suspension was gently stirred at 21°C. The aqueous suspension extrudate was then exposed to up to 90°C for 15 minutes. The heated aqueous suspension extrudate was then cast onto a flat surface and dried at 60°C under a vacuum of 15 inHg.

[0218] A "silk glycerol emulsion film" was formed using recombinant spider silk emulsion created using the process described in Example 8. Specifically, a mixture of 25% by weight recombinant spider silk polypeptide powder and 75% by weight glycerol was circulated in a twin screw extruder at 90° C. and 250 RPM for 30 minutes to produce recombinant spider silk extrudates. The recombinant spider silk extrudates were resuspended in water, stirred, and mixed with an emulsion containing the following ingredients: water, glycerin, pentylene, glycol, silk proteins, ceramide AP, ceramide EOP, ceramide NP, sodium hyaluronate, sodium lauroyl lactylate (SLL), cholesterol, xanthan gum, sclerotium gum, lecithin, pullulan, carbomer, hexylene, glycol, ethylhexylglycerin, caprylyl glycol, disodium EDTA, and phenoxyethanol.

[0219] The emulsion was then poured onto a flat surface and dried at 60° C. for 4 hours.

[0220] A "silk glycerol emulsion freeze-dried film" was formed using recombinant spider silk extrudates produced using the process described in Example 8. Specifically, a mixture of 25% by weight recombinant spider silk polypeptide powder and 75% by weight glycerol was circulated in a twin screw extruder at 90°C and 250 RPM for 30 minutes to produce recombinant spider silk extrudates. The recombinant spider silk extrudates were mixed with an emulsion containing the following components: water, glycerin, pentylene, glycol, silk proteins, ceramide AP, ceramide EOP, ceramide NP, sodium hyaluronate, sodium lauroyl lactylate (SLL), cholesterol, xantham gum, sclerotium gum, lecithin, pullulan, carbomer, hexylene, glycol, ethylhexylglycerin, caprylyl, glycol disodium EDTA, and phenoxyethanol. The emulsion was then poured onto a flat surface and then placed in a Labconco freeze dryer and exposed to -106°C at 0.008 mBar for 4 hours until the water sublimed. Upon freeze drying, a "spongy" or porous mixture was obtained.

[0221] Each of the silk glycerin film, silk glycerin emulsion film, and silk glycerin emulsion freeze-dried film was applied to the skin of a test subject for testing. When in contact with the skin and water was added, the film formed a dispersible liquid, which was absorbed by the skin. Figure 19 shows the above process for producing a dried silk glycerin emulsion film and its application to the skin of a test subject. Figure 20 shows the steps involved in the production of a silk glycerin emulsion freeze-dried film and its application to the skin of a test subject.

[0222] Example 11: Comparison of recombinant spider silk extrudates with non-extruded silk-glycerol mixtures The film-forming ability of recombinant spider silk extrudates was investigated in comparison to a mixture of non-extruded silk and glycerol. As a first step, recombinant spider silk extrudates were produced using the method described above in Example 8, comprising 25% recombinant spider silk polypeptide powder and 75% glycerol by weight. Specifically, a mixture of 25% recombinant spider silk polypeptide powder and 75% glycerol by weight was circulated in a twin-screw extruder at 90° C. and 250 RPM for 30 minutes to produce recombinant spider silk extrudates. Aqueous suspension extrudates were produced by forming a composition with 10% recombinant spider silk extrudate by weight in 90% deionized water by weight. The aqueous suspension extrudates were heated to 90° C. and then dried on a flat surface. As shown in FIG. 21, the dried mixture formed a solid film that was peelable from the surface on which it was cast.

[0223] For comparison, a "slurry" mixture containing 25% by weight of recombinant spider silk polypeptide powder and 75% by weight of glycerol was created by mixing recombinant spider silk polypeptide powder with glycerol to form a viscous slurry. The slurry mixture was suspended in an aqueous solution containing 90% deionized water and 10% of the slurry mixture. The suspension of the slurry mixture was then heated to 90°C and then dried on a flat surface to determine whether the slurry mixture would form a film. As shown in FIG. 21, when the aqueous suspension of the slurry mixture was dried, a viscous slurry similar to the previous slurry mixture that was observed for the aqueous suspension was observed. Thus, the step of forming an extrudate is beneficial for the film-forming properties of the mixture.

[0224] To further investigate the film-forming properties of the mixtures, each of the 25% silk / 75% glycerol extrudate and 25% silk / 75% glycerol slurry (non-extrudate) was mixed with an emulsion containing the following components: water, glycerin, pentylene, glycol, silk proteins, ceramide AP, ceramide EOP, ceramide NP, sodium hyaluronate, sodium lauroyl lactylate (SLL), cholesterol, xantham gum, sclerotium gum, lecithin, pullulan, carbomer, hexylene, glycol, ethylhexylglycerin, caprylyl, glycol disodium EDTA, and phenoxyethanol. Both formulations were then dried on a flat surface at 60° C. for 4 hours to determine whether film formation was observed upon drying. As shown in FIG. 22, the formulation containing the emulsion and recombinant spider silk extrudate formed a film upon drying. However, no film was observed upon drying of the formulation containing the emulsion and recombinant spider silk polypeptide powder. Thus, the formation of an extrudate is beneficial to the film-forming properties of the emulsion mixture.

[0225] Example 12: Silk extrusion with methanol In this experiment, 25 wt% powder was mixed with 75 wt% glycerin to prepare extrudates and processed in a twin screw extruder at 90° C. and 250 rpm for 30 minutes. The extrudates were then diluted 5-fold in water and resuspended with gentle mixing at room temperature. The mixture was split into two aliquots. One aliquot was further diluted 5-fold in water and then the other aliquot was diluted 5-fold in methanol. As shown in FIG. 23, the sample diluted with water did not show any phase change as evident from visual and microscopic inspection. The sample diluted with methanol did show a phase change, the mixture became opaque in appearance, and aggregation was evident under a microscope. This result highlights that while the FTIR spectroscopic profiles of the extrudate material and powder are similar (including similar b-sheet content before and after methanol treatment), the extrudate is unique in that the methanol treatment induces aggregation.

[0226] A water-suspended extrudate was prepared anew and separated into two aliquots as described above. Each aliquot was poured into a flat surface weight boat and allowed to dry overnight at ambient room temperature and humidity. This resulted in a thin film material from each aliquot. One film was left untreated, while the other was exposed to methanol vapor overnight in a closed chamber. The films were then peeled off and applied to skin. The untreated film was easily rubbed into the skin with gentle pressure and shifted. The methanol-treated film remained largely intact. Pressure and shear forces were applied to the methanol-treated film, causing it to fracture and roll over the skin. Continued pressure and shear forces eventually allowed the fractured film pieces to be rubbed into the skin. FTIR spectra showed no difference in beta-sheet content between the two films, although the relative ratio of β-sheet content to glycerin was slightly reduced. This suggests that methanol can replace the glycerol bonds to the silk proteins and increase the intermolecular entanglements, which explains why the films have different textures.

[0227] Example 13: FTIR analysis of extruded and non-extruded silk compositions FTIR analysis was used to characterize the recombinant spider silk extrudates under the following conditions: Glycerin: 100% glycerin sample Powder: 100% powder sample Powder + glycerin: Powder was suspended in glycerin at 25% by weight powder and 75% by weight glycerin. ● Annealed with powder + glycerin > methanol: The powder was suspended in glycerin at 25 wt% powder, 75 wt% glycerin, and then immersed in methanol for 3 hours. After 3 hours, the methanol was dried off. Extrudate: 25% by weight of powder, 75% by weight of glycerin were mixed and processed in a twin screw extruder at 90° C., 250 rpm for 30 minutes. ● Extrudate > Resuspension Drying: The extrudate was resuspended by diluting with 5 times water at room temperature with gentle mixing. The resuspended extrudate was then dried overnight at ambient temperature and humidity. Extrudates annealed in methanol: The extrudates were immersed in methanol for 3 hours. After 3 hours, the methanol was dried off. Extrudate > Resuspension Drying > Annealed in Methanol: The extrudate-resuspension material was immersed in methanol for 3 hours. After 3 hours, the methanol was dried off.

[0228] The FTIR spectra of each were analyzed for β-sheet content and the 1637-1700 cm -1 1620-1625 cm for total protein content at -1 The amounts of beta-sheet content were reported as the relative amounts of beta-sheet content at 100 nm.

[0229] The spectra are shown in Figure 25A and the quantification of relative beta-sheet content is shown in Figure 25B, including the statistical analysis, for which the upper and lower green diamonds represent the 95% confidence interval. The overlapping diamonds are displayed as lines above and below the group mean, and

number

[0230] In this analysis, the extrudate samples (extrudate, extrudate > resuspension drying, and extrudate > resuspension drying > methanol annealed) are not statistically different from the powder + glycerin sample. This indicates that the process that transforms the powder into the extrudate does not affect the beta-sheet motif. Rather, other mechanisms are required to explain the phase change between the powder and the extrudate. This is further clarified by comparing the samples treated with methanol. Methanol is a common coagulant for silk, which transforms the crystalline regions of silk from an amorphous configuration to a beta-sheet configuration. No difference in beta-sheet content was measured between the untreated and methanol-treated samples, further clarifying that the mechanism by which the extrusion process transforms the powder into the extrudate is not dominated by beta-sheet perturbation. FTIR spectra show no difference in beta-sheet content between these two films, although the relative ratio of amino acid content (i.e., amide I band) to glycerin is slightly reduced (Figure 25C).

[0231] FTIR analysis was used to characterize the concentration of recombinant spider silk extrudates in aqueous suspension after drying to determine whether the water content of the aqueous suspension extrudates affected solubility. Spider silk extrudates of 25% recombinant spider silk polypeptide powder and 75% glycerol were suspended in various aqueous solutions to achieve final weight amounts of 5%, 10%, 15%, and 20% recombinant spider silk polypeptide. The aqueous suspension extrudates were then dried and FTIR was evaluated using the method described above. Figure 26 shows the viscosity and FTIR peaks of the dried aqueous suspension extrudates. As shown in Figure 26, significant differences were observed in the viscosity of the dried aqueous suspension extrudates. However, the FTIR peaks corresponding to beta-sheet content were similar between the different aqueous suspension extrudates, indicating that the amount of beta-sheet formation did not change depending on the water content in the aqueous suspension extrudates.

[0232] Example 14: Recombinant silk colloidal suspension in extrudate supernatant The intent of this example is to quantitatively describe the material properties of the present invention and to illustrate their differences from recombinant silk in powder form. When the extrudates are suspended in aqueous media, they become colloidal suspensions as determined by particle sorting. This is completely different from the powder, which does not significantly partition into the aqueous phase when suspended in aqueous media, as evidenced by size exclusion chromatography (SEC).

[0233] Colloidal suspensions of recombinant silk were prepared by mixing the extrudate with water and centrifuging the mixture to produce a supernatant containing the colloidal suspension. The protein content in the extrudate supernatant was analyzed by size exclusion chromatography (SEC) and compared to the protein content in silk powder, silk powder supernatant, and extrudate. The size distribution of particles in the colloidal suspension was measured and compared to a 200 nm size standard, a glycerol control, and silk solubilized using LiBr. Details of sample preparation and assay results are provided below.

[0234] Silk extrudate supernatant The extrudate supernatant was prepared by suspending the extrudate (75% glycerin and 25% silk) in 20% by weight water (15% glycerin and 5% silk) and shaking alternately with both hands for approximately 5 minutes and vortexing until the solids completely disappeared. The mixture was incubated at RT for 30 minutes. The mixture was centrifuged at 16,000 RCF for 30 minutes to remove the solids. The supernatant was collected and named as extrudate supernatant.

[0235] Silk powder supernatant The powder supernatant was prepared by suspending the silk powder prepared in Example 1 in 5 wt% water and incubating at room temperature for 30 minutes. The mixture was centrifuged at 16,000 RCF for 30 minutes to remove the silk powder solids. The supernatant was collected and named as powder supernatant.

[0236] Solubilization of LiBr silk To provide a highly solubilized silk sample as a control, for 18B silk powder, 1 g of powder was suspended in 9.3 M LiBr aqueous solution to 4 mL of LiBr solution. This solution was incubated at 60° C. for 4 hours. The dissolved silk was loaded into a dialysis cassette with a 3,500 MW cutoff and dialyzed against 4 L of DI water for 48 hours, changing the water six times during dialysis. The dialyzed silk solution was then centrifuged at 16,000 RCF for 30 minutes to remove any precipitated silk. The remaining highly solubilized silk sample was then assayed for particle sorting as described below.

[0237] Protein Profile The protein profiles of silk powder, silk powder supernatant, silk extrudate, and silk extrudate supernatant were measured by SEC. The results are shown in FIG. 27 and provided in Table 16. The powder, extrudate, and extrusion supernatant samples have similar protein profiles. Thus, the silk material in the extrudate supernatant fraction is similar in protein composition to the powder and extrudate. In other words, no particular aggregates, full-length molecules, or low molecular weight (LMW) fractions are preferentially transferred to the extrudate supernatant. Also, the powder supernatant contained undetectable levels of protein, indicating that the protein from the powder was not solubilized in the supernatant. Furthermore, the protein weight percent content in the extrudate supernatant was 5%, the same as the extrudate and powder, indicating that the portion of silk that formed colloids was not reduced compared to the starting mixture concentration. [Table 16]

[0238] Particle Sorting Particle sorting was performed on a Malvern instrument Zetasizer Nano. Polystyrene polymer 200 nm standards were dissolved in 250 times water. All samples were diluted with 250 times the starting solution in deionized water (initial silk content was 5 wt. % and glycerin content was 15 wt. %). Samples were poured once and measurements were performed in triplicate. Data reported are z-average in nanometers and are accompanied by the polydispersity index (PdI) (Figure 28 and Table 17). Polydispersity index values ​​approaching zero mean particle size are obtained from a single population and values ​​approaching one mean particle size are obtained from multiple populations.

[0239] Because SEC does not distinguish between solubilized and non-solubilized silk, particle sorting was performed to elucidate the nature of the molecular assembly in the extrudate supernatant (i.e., to determine whether the molecules aggregated into particles and the size of the particles).

[0240] As expected, the glycerin and LiBr controls showed no peaks; these are fully soluble solutions and do not show any peaks. The extrudate supernatant showed two peaks and a shoulder region (Figure 28). The peaks correspond to diameters of 38 nm and 642 nm, and the shoulder diameter is approximately 150 nm. Considering that a colloid is defined as "a mixture having particles in the range of 1-1000 nanometers in diameter yet capable of remaining uniformly distributed throughout the solution," this data indicates that the extrudates resuspended in water formed a colloidal phase in addition to the undissolved gel phase.

[0241] This result is further confirmed by visual inspection of the powder and extrudate mixtures (Figure 29). The 5% silk powder mixture settled after 24 hours of incubation at 4° C. The 5% silk extrudate supernatant (i.e., the gel phase was centrifuged, which was 5% silk and 15% glycerin by weight) did not settle even after 30 days of incubation at 4° C. [Table 17]

[0242] Example 15: Barrier repair assay Six subjects (mean age 38.2 years; 5 females-1 male) were tested for skin barrier repair using a 5% silk protein extrudate mixture (extrudate added to the mixture was 75% glycerin and 25% silk protein, resulting mixture was 15% glycerin and 5% silk protein). Three compartments were defined on the volar forearm. Transepidermal water loss (TEWL) was measured with a moisture evaporometer. Skin was tape-removed using duct tape until TEWL values ​​reached 20-25. The product was applied and TEWL was measured again at 30 minutes and 2 hours. Vehicle control (containing 15% glycerin) and untreated sites were also included in the study.

[0243] The 5% extrudate sample showed the most rapid healing compared to the control and also returned to baseline more quickly than the control (Figure 30).

Claims

1. 1. A method for producing a silk-based emulsion comprising: mixing said composition by applying pressure and shear forces to a composition comprising 10-33% recombinant spider silk polypeptide powder by weight of the composition and 67-90% glycerol by weight of the composition, thereby converting said composition into an extrudate; suspending at least a portion of the extrudate in an aqueous solvent to form an aqueous extrudate suspension; Providing an emulsion; and mixing said aqueous extrudate suspension with said emulsion to form said silk-based emulsion; The method comprising:

2. The method of claim 1 , wherein the extrudate is substantially homogeneous.

3. The method according to claim 1 , wherein the silk-based emulsion is a cosmetic or skin care formulation.

4. 1. A method for producing a silk-based solid or gel, comprising: mixing a composition comprising recombinant spider silk polypeptide powder and glycerol by applying pressure and shear forces to said composition, thereby converting said composition into an extrudate; suspending the extrudate in an aqueous solvent to form an aqueous extrudate suspension; and drying the aqueous extrudate suspension to form the silk-based solid or gel. The method comprising:

5. 5. The method of claim 4, further comprising coagulating the aqueous extrudate suspension to form coagulated silk in the suspension.

6. The method of claim 4, wherein the silk-based solid or gel is a film.

7. 7. The method of claim 6, wherein the silk-based solid is a cosmetic or skin care preparation.

Citation Information

Patent Citations

  • Preparation method for regenerated fibroin fiber

    CN102181957A

  • Encapsulation of cosmetic fragrances and / or food fragrances into silk fibroin biomaterials

    JP2015525767A

  • Method for Producing Polymer Aggregate

    US20190002644A1

  • Method and apparatus for spinning spider silk protein

    WO2004090205A2

  • Method for producing polymer aggregate

    WO2017110922A1